Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

An end-to-end model framework for understanding and predicting changes in Antarctic marine ecosystems - Ilari Stollberg; Sophie Bestley; Andrew Constable; Elizabeth A. Fulton; Javier Porobic; David Green; Denise O’Sullivan; Mao Mori; Stuart Corney; Michael Sumner; Jessica Melbourne-Thomas (Ecological Modelling, 2026)

Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Stable isotope insights into the habitat use of two benthic invertebrates along Antarctic glacier-influenced fjords - Pau Bardi-Puigdefàbregas; Miguel Bascur; David K.A. Barnes; Stuart Jenkins; Carlos P. Muñoz-Ramírez; Estefanía Rodríguez; Antonio Brante; Luis Cardona; Conxita Avila (Marine Environmental Research, 2026)

Swimming in urban estuaries: Understanding stormwater contamination events and recovery from historical data - Simon D. Lloyd; Josef I. Bisits; Gordana Popovic; Paul Osmond; David J. Roser; Stuart J. Khan (Water Research, 2026)

Camizestrant-induced heart rate reduction is mediated via a sinoatrial node pacemaker channel mechanism - Andrew Hall; Saïd El-Haou; Inmaculada C. Villar; David Molla; Maggie Kwan; Stuart Purbrick; David Henry; Jason Kirk; Glen Hawthorne; Serena Canzolino; Joanna Harding; Alexander Harmer; et al. (Toxicology and Applied Pharmacology, 2026)

Evaluating options to mitigate hydropower impacts on river thermal regimes in a changing climate - David Dorthe; Michael Pfister; Stuart N. Lane (Science of The Total Environment, 2026)

Chlorinated organophosphate esters in Brazilian solid waste: concentrations, national load estimates, and regulatory implications for a circular economy - Hansel David Burgos Melo; Rafael Veronez; Juliana de Souza-Araujo; Angie Paola Santacruz Salas; Olumide Emmanuel Akinrinade; Sandro Donnini Mancini; Daniel Drage; Stuart Harrad; André Henrique Rosa (Environmental Pollution, 2026)

Hyperspectral remote sensing for monitoring coral reef and seagrass Ecosystems: capabilities, limitations and future directions - Joanna N. Smart; Dylan Cowley; David E. Carrasco Rivera; Muhammed Hafizt; Mitchell Lyons; Stuart Phinn; Chris Roelfsema (Marine Environmental Research, 2026)

Distribution characteristics and ecotoxicological risks of typical organic flame retardants and plasticisers in the Amazon River basin around Manaus, Brazil - Yulong Ma; Angie Paola Santacruz Salas; Hansel David Burgos Melo; Shijie Wang; Jingxi Jin; Ezio Sargentini Júnior; André Henrique Rosa; Stuart Harrad (Environmental Research, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Prevalence of traded bird species in key biodiversity areas - Oscar Morton; Tom Lansley; Stuart H. M. Butchart; Graeme M. Buchanan; David P. Edwards (Conservation Biology, 2026)
The use and trade of biodiversity involve tens of thousands of species that are exploited at a range of scales, intensities, and degrees of sustainability. As a result, some are highly threatened. Key biodiversity areas (KBAs) are sites of significance for the persistence of biodiversity identified nationally based on standardized criteria. The degree to which biodiversity in KBAs is likely to be used and traded is not well understood. We undertook a fine‐scale assessment of the area of habitat (AOH) of traded species in KBAs. We used data on >16,000 KBAs and combined these with AOH maps for >10,000 bird species, a heavily traded and well‐documented indicator taxon. We subsequently mapped and quantified the distribution of traded species richness, extinction risk, and range‐size rarity in and adjacent to KBAs. Although less than half of all bird species are traded, we found that most bird species in KBAs were traded, and the richness of traded species was more than twice (119%) that of nontraded species. Traded species had comparable proportions of their AOH (22.5% on average) in KBAs as nontraded species (21.5%). Global hotspots of richness, extinction risk, and range rarity for traded species disproportionately occurred in KBAs, which had higher levels of extinction risk and range rarity for traded species than locations immediately outside KBAs. Of the 46 species that are likely threatened by unsustainable use and have the majority of their habitat falling within KBAs, we found that eight species had no habitat in designated protected areas. Reconciling sustainable use and the critical importance of KBAs for threatened species is essential. Our results suggest that for some species, there is an urgent need to protect key sites and ensure that any use and trade of species within them are sustainable.

Hybrid particulate matter generated by lava-ignited wildfires at the Litli-Hrútur 2023 eruption, Iceland - Laura Wainman; Evgenia Ilyinskaya; Melissa Anne Pfeffer; Penny E. Wieser; David Damby; James B. McQuaid; Celine Mandon; Enikö Bali; Josefa Sepulveda-Araya; Richard Walshaw; Caleb Hall; Stuart Micklethwaite; et al. (Science of The Total Environment, 2026)

Agricultural nitrous oxide emissions across twenty years of micrometeorological observations show trends associated with soil freezing and fertilizer application - Leah Brown; Ian B. Strachan; David E. Pelster; Stuart Admiral; Luc Pelletier; Brian Grant; Ward Smith; Elizabeth Pattey (Science of The Total Environment, 2026)

Chlorophyll deficient barley xan-n mutants are defective in an essential superoxide dismutase - Anna San Torcuato; David Stuart; Otto Nordling; Kasim Khan; Shakhira Zakhrabekova; Mats Hansson (Plant Science, 2026)

Static Alternating Field Demagnetization of Rocks: Why Three Axes are not Enough - David Finn; Stuart A. Gilder; Dario Bilardello; Michael R. Wack; Robert S. Coe; Michael Jackson; Wyn Williams; Leon Kaub; Michael J. Branney (Studia Geophysica et Geodaetica, 2026)
Paleomagnetism relies4 on stable remanent magnetizations held in rocks to reconstruct the ancient geomagnetic field direction and intensity. However, rocks may carry secondary overprints that obscure or completely destroy the original signal. To study the stability of the magnetic vector(s), laboratories routinely apply static alternating field demagnetization along three orthogonal axes (AFD₃), which is fast, non-destructive, and easy to automate. Here, we present a multiparticle model that shows AFD₃ can deviate the natural remanent magnetization (NRM). Deviations can be avoided when fulfilling two conditions: (i) the NRM was acquired in a weak field where magnetization intensity varies linearly with field strength, and (ii) the sample is magnetically isotropic. The first condition is generally satisfied for rocks holding thermal or detrital remanent magnetizations, but not those affected by an isothermal remanence (e.g., lightning), even though AFD₃ is often used to remove them. In rocks with an anisotropic particle orientation distribution, stepwise AFD₃ progressively removes different coercivity subpopulations as a function of grain orientation so the effective remanence anisotropy of the surviving carriers changes during demagnetization. The anisotropy-driven deflection therefore evolves with AF step, producing curvilinear demagnetization trajectories. Our theoretical results argue for caution when applying AFD₃ to anisotropic samples or those with isothermal overprints. Undesired NRM rotation can be avoided by tumble demagnetization or mitigated by increasing the number of alternating field axis orientations.

Non-Tensorial Anhysteretic Remanent Anisotropy and the Detection of Composite Fabrics - David Finn; Michael R. Wack; Stuart A. Gilder; Michael Jackson; Robert S. Coe; Dario Bilardello; Leon Kaub; Wyn Williams; Michael J. Branney (Studia Geophysica et Geodaetica, 2026)
The anisotropy of anhysteretic remanent magnetization (AARM) provides a powerful, nondestructive means of assessing magnetic fabrics. It is widely applied to infer strain and emplacement conditions in sedimentary, volcanic, and intrusive rocks. AARM is generally represented by a symmetric second-rank tensor describing its orientation, strength, and shape. AARM, however, departs from a tensorial shape when the number of grains carrying each directionally imparted anhysteretic remanence (ARM) varies with ARM orientation – a condition that arises when the alternating field (AF) over which the ARM is imparted does not fully activate the sample. Experimental data from a highly anisotropic ignimbrite sample, together with multiparticle modeling, show that such partial activation produces non-tensorial AARMs. Although this behavior complicates tensor analysis, non-tensorial AARM can reveal superimposed fabrics, provided that users can apply AF and ARM in a broad range of orientations. This article presents theoretical models that demonstrate non-tensorial behavior and explains how to utilize these properties to discern superimposed fabrics in natural samples.

Rethinking trophic transfer efficiency in freshwater ecosystems: Current understanding and knowledge gaps - Hua Song; Fen Guo; David Dudgeon; Xiaoguang Ouyang; Feilong Li; Siyong Wu; Zhenmin Yang; Wei Gao; Yuan Zhang; Stuart E. Bunn (Limnology and Oceanography, 2026)
Trophic transfer efficiency (TTE) represents the proportion of energy transferred between consecutive trophic levels within a food web. Though it is a fundamental property that shapes energy flow across all ecosystem types, a comprehensive understanding of TTE in freshwater ecosystems is still lacking. This review evaluated common estimation methods, identified key influencing factors, and outlined future research priorities based on a global freshwater TTE dataset. Methods to estimate TTE include production estimates, carbon‐transfer measurements, model‐based approaches, and predator–prey mass‐ratio estimates; mixed‐effects analyses indicate that method choice significantly structures reported TTE, yet each method has limitations in accuracy and consistency. Trophic transfer efficiency also varies across ecosystem types, consistent with systematic differences in the environmental and biological controls on energy transfer among systems. Light, nutrients, and organic matter affect TTE by altering the abundance and composition of primary producers, whereas food quality, temperature, and dissolved oxygen impact TTE by modulating consumer growth and metabolism of individual consumers. At the community and ecosystem levels, predation pressure, competition, species richness, the presence of non‐native species, and cross‐ecosystem interactions shape community structure, thus affecting TTE. Better understanding of TTE in freshwater ecosystems will depend on refined estimation methods and integration of new techniques, such as remote sensing and stable‐isotope labeling, to improve TTE estimates. Research priorities include understanding the synergistic effects of anthropogenic pressures and climate change on TTE, investigating how food quality and individual‐level metabolic processes govern TTE, and examining the influence of cross‐ecosystem energy fluxes on TTE dynamics. It is essential to recognize that TTE varies among trophic levels and cannot be represented by a single value along the entire food chain. Our synthesis reveals that more research is needed in the tropics and the southern hemisphere to expand our understanding of global variability in TTE. This would facilitate greater use of TTE as an indicator of ecological change or the restoration of efficient energy transfer through freshwater food webs.

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Divergent demographic responses of boreal-breeding ducks to growing season variability - David J. Messmer; Stuart Slattery; Mark C. Drever; Chris Derksen; Robert G. Clark (Oecologia, 2026)
In seasonal environments climatic variability shapes the timing, duration, and magnitude of primary production with effects that may percolate upward through food chains. While the role of spring phenology and implications of trophic mismatches have been documented in some bird species, including waterfowl, there is little research on the role of growing season duration or overall productivity. Duck species breeding in the western boreal forest (WBF) of North America vary widely in their average timing and plasticity for breeding dates, which may set up differing sensitivity to spring phenology. In contrast, increases in growing season duration and productivity may positively impact species regardless of life history through the extension of the breeding season and bottom-up trophic enrichment. We tested these hypotheses using breeding population estimates for 8 species (or species groups) of ducks and normalized difference vegetation index to infer spring phenology, length of growing season, and growing season productivity for duck survey areas in the WBF, 1982–2019. Spring phenology had mixed effects on species’ population growth rates, and effects were generally not consistent with mediation by average breeding dates or plasticity. Length of season and productivity effects showed some species’ population growth rates decreasing following longer seasons or higher productivity, opposite our predictions. These results suggest that, for secondary consumers like ducks, the role of growing season characteristics may be mediated or superseded by more complex biotic and abiotic interactions than can be explained with simple annual summaries of growing season characteristics.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Multi-scale observations during the 2024 mass coral bleaching event on Heron Reef, Australia - Devin A. Rowell; Nicholas M. Hammerman; Kirsten M. Golding; Tania Marie Kenyon; Zoe Meziere; Courtney Morgans; Kristen Taylor Brown; Faye F. Diederiks; David E. Carrasco Rivera; Karen Eigeland; Roima Paewai-Huggins; Kathryn Markey; et al. (Marine Biology, 2026)

A Beginner's Guide to Structural Variants in Eco‐Evolutionary Population Genomics - Katarina C. Stuart; Rebekah A. Oomen; Anna Tigano; Maren Wellenreuther; Jana Wold; David L. Field; Claire Mérot (Molecular Ecology, 2026)
Whole‐genome sequencing (WGS) has greatly expanded researchers' ability to study structural variants (SVs), that is, the variation in the presence, number, orientation or position of a DNA sequence. This has paved the way to study the eco‐evolutionary dynamics of SVs across the tree of life and within a population genomics framework. In this review, we provide the necessary fundamentals to help researchers generate and analyse population‐level SV data. We discuss the unique properties of different SV groups and how these fundamental differences interact with important biological and evolutionary processes using both empirical results and theory. This includes discussion of unresolved issues around SVs, such as technical difficulties in identification, accounting for diversity and evaluating functional effects. We explicitly integrate into this discussion transposable elements, which are an important component of SVs often identified in population‐level variant data. Finally, we focus on the practical side of SV analysis, offering a framework for SV identification and data analysis. In particular, we examine the heterogeneous nature of SV properties (type, length, sequence identity) that should be considered when studying them in ecology and evolution. This review aims to provide resources and guidelines to help researchers navigate the complexities of a relatively new field of eco‐evolutionary genomics research.

PBDE concentrations in wastes from construction and demolition, soft furnishings, and end-of-life vehicles in Brazil - Hansel David Burgos Melo; Juliana de Souza-Araujo; Rafael Cardoso; Daniele Frascareli; Erik Sartori Jeunon Gontijo; Sandro Donnini Mancini; Stuart Harrad; André Henrique Rosa (Environmental Research, 2025)

He, Ne, and Ar isotope systematics in Chang’e-5 plagioclase reveal diffusive loss and reirradiation processes - Xuhang Zhang; Fei Su; Guillaume Avice; David V. Bekaert; Tomoya Obase; Yuta Otsuki; Finlay M. Stuart; Yingnan Zhang; Jiayan Nie; Xiaoguang Li; Runqing Zhou; Ziheng Liu; et al. (Earth and Planetary Science Letters, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

The first report of Hematodinium perezi genotype I infection of Chinese mitten crab (Eriocheir sinensis) from the River Thames, UK - Rose C. Kerr; Hamish J. Small; David Bass; Wafa S. Al Arimi; Stuart Ross; Roland Pevsner; Bryony Williams; Ronny van Aerle; Grant Stentiford; Kelly Bateman (Journal of Invertebrate Pathology, 2025)

Most landfill methane emissions Escape detection in EPA21 surface emission monitoring surveys - Athar Omidi; Evelise Bourlon; Afshan Khaleghi; Nadia Tarakki; Rebecca Martino; Jordan Stuart; David Risk (Waste Management, 2025)

Comparative analysis of the temporal abundance of the epiphytic pest, Melanothamnus thailandicus, affecting farmed Kappaphycus striatus: Visual and molecular detection approaches - Joseph P. Faisan; Rema C. Sibonga; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Jonalyn P. Mateo; Janina Brakel; Juliet Brodie; Georgia M. Ward; David Bass; Stuart Ross; Grant D. Stentiford; Claire Gachon; et al. (Journal of Applied Phycology, 2025)

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Modelling and mapping of subsurface nitrate-attenuation index in agricultural landscapes - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne (Journal of Environmental Management, 2025)

Elevation-dependent breakpoint in climate forcing of tree growth in the Turtmann River Basin, Switzerland - Nazimul Islam; Torsten Vennemann; David Meko; Stuart Lane (Dendrochronologia, 2025)

The Itremo Massif Protected Area in the Central Highlands of Madagascar — a plant species checklist - Franck Rakotonasolo; Landy R. Rajaovelona; Andry A. Rakotoarisoa; Fitiavana Rasaminirina; Nantenaina H. Rakotomalala; Ary Misa Andry; Velosoa Razafiniary; Henintsoa Razanajatovo; Nomentsoa Randriamamonjy; Vonona Randrianasolo; Olinirina P. Nanjarisoa; Solofo E. Rakotoarisoa; et al. (Kew Bulletin, 2025)
Summary The Itremo Massif Protected Area was established and is managed by Kew Madagascar. Here, we publish a plant species checklist of the Itremo Massif Protected Area. It is one of the first expert-verified plant species checklists to be generated for a protected area in Madagascar and includes 749 plant species, 353 genera and 103 families. For each species, full synonymy, notes on vernacular names, global distribution, distribution in Madagascar, elevation, habitat and ecology, flowering period, conservation status and specimen lists are provided.

Conservation changed but not divided - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Amy Hinsley; Sadiq Jaffer; et al. (Trends in Ecology & Evolution, 2025)

Vehicles kill birds on sandy beaches: The global evidence - Thomas A. Schlacher; Michael A. Weston; Brooke Maslo; Jenifer E. Dugan; Kyle A. Emery; David M. Hubbard; Brendan P. Kelaher; Mariano Lastra; Stuart E. Parsons (Science of The Total Environment, 2025)

Unraveling composite magnetic fabrics through tensor decomposition - David Finn; Josef Jezek; Stuart A. Gilder; Michael R. Wack; Felix Ostermeier; Michael Jackson; Robert S. Coe; Michael J. Branney (Physics of the Earth and Planetary Interiors, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Yellow barley xan-m mutants are deficient in the motor unit SECA1 of the SEC1 translocase system - David Stuart; Anastasiia Ivanova; Shakhira Zakhrabekova; Mats Hansson (Planta, 2025)
Main conclusion Chloroplast protein transport depends on the SEC1 translocase. Barley xan-m mutants, deficient in SECA1, lack chlorophyll and die as seedlings. Their yellow phenotype indicates that carotenoid chemistry is less SEC1-dependent. Chloroplast proteins encoded by genes located in the cell nucleus need to be transported across up to three chloroplast membranes to find its correct location. SEC1 is one of the major translocase systems. In plants, SEC1 consists of three proteins (SECA1, SECY1 and SECE1) and transports substrate proteins over the thylakoid membrane. SECA1 is an ATPase that delivers the substrate protein to the SECY1–SECE1 channel. In the present study, we analyzed five allelic barley xan-m mutants, which had been isolated between 1925 and 1957. The mutants belong to a larger collection of barley mutants deficient in chlorophyll biosynthesis and chloroplast development. Mutations in the xan-m gene are recessive and result in a yellow phenotype due to lack of chlorophyll and presence of carotenoids. Mutant seedlings die after approximately 10 days. We identified the defective gene in the xan-m mutants by a variant of bulk segregant analysis. The gene xan-m is an orthologue of SECA1 in Arabidopsis. Previously, only genes related to chlorophyll biosynthesis have been identified in the collection of barley xan mutants. The yellow phenotype of the mutants demonstrates that proteins responsible for carotenoid biosynthesis and storage are not or less dependent on an intact SEC1 translocase.

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

The potential for AI to revolutionize conservation: a horizon scan - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Francis Gassert; Amy Hinsley; et al. (Trends in Ecology & Evolution, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Timeline of fatty acid incorporation from diet to egg in California yellowtail Seriola dorsalis - Li Sun Chin; David Bradshaw; Paul S. Wills; Kevin Stuart; Mark Drawbridge; Sahar Mejri (Aquaculture, 2025)

Adverse impacts of off-road vehicles on coastal dune vegetation are widespread, substantial, and long-lasting: Evidence from a global meta-analysis of sandy beach-dune systems - Thomas A. Schlacher; Michael A. Weston; Shane Orchard; Brendan P. Kelaher; Brooke Maslo; Jenifer E. Dugan; David M. Hubbard; Leonardo Costa; Melanie J. Bishop; Kristal N. Kostoglu; Ben L. Gilby; Christofer J. Henderson; et al. (Estuarine, Coastal and Shelf Science, 2025)

First cycle or polycyclic? Combining apatite and zircon detrital U-Pb geochronology and geochemistry to assess sediment recycling and effects of weathering - Emily S. Finzel; Stuart N. Thomson; David M. Pearson; L．Kenneth Horkley; Kacey Garber; Cole Gardner (Earth and Planetary Science Letters, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Assessment of spatial variability and temporal stability of groundwater redox conditions in New Zealand - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne; Jon K. F. Roygard (Environmental Monitoring and Assessment, 2024)

Increased monetary equity and health wellbeing benefits for marginal urban socioeconomic groups from access to green space - Adam Loch; Stuart Sexton; John Maclean; Patrick O’Connor; David Adamson; Glen Scholz (Urban Forestry & Urban Greening, 2024)

Widespread upper-ocean deoxygenation in the Alpine-Mediterranean Tethys during the Toarcian Oceanic Anoxic Event - Wenhan Chen; David B. Kemp; Hugh C. Jenkyns; Stuart A. Robinson; Shouyi Jiang; Chengrong Pan; Chao Li (Global and Planetary Change, 2024)

Vegetation recovery of rehabilitated pasture at three coal mine sites following fire disturbance - Phillip B. McKenna; David Doley; Natasha Ufer; Vanessa Glenn; Stuart Phinn; Peter D. Erskine (Ecological Engineering, 2024)

Unifying Coral Reef States Through Space and Time Reveals a Changing Ecosystem - Simon J. Brandl; Jérémy Carlot; Rick D. Stuart‐Smith; Sally A. Keith; Nicholas A. J. Graham; Graham J. Edgar; Jérémy Wicquart; Shaun K. Wilson; Rucha Karkarey; Mary K. Donovan; Jesus E. Arias‐Gonzalez; Rohan Arthur; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological state shifts that alter the structure and function of entire ecosystems are a concerning consequence of human impact. Yet, when, where and why discrete ecological states emerge remains difficult to predict and monitor, especially in high‐diversity systems. We sought to quantify state shifts and their drivers through space and time in the most ecologically complex marine ecosystem: tropical coral reefs. Location Worldwide. Time Period 1987–2019. Major Taxa Studied Coral reef communities. Methods Using a global dataset of 3375 coral reef surveys, along with 13 time series datasets ranging between 1987 and 2019, we applied a novel double‐dichotomy approach to classify coral reefs into four simplified and discrete states based on the relative contributions of corals versus algae to benthic cover and small‐bodied versus large‐bodied fishes to fish standing stock. We then examined state shifts considering a range of spatial predictors and tested whether states have shifted directionally over time, and the nature of the most common transitions. Results We show that geographic, environmental and anthropogenic context fundamentally shapes coral reef states at the local scale, which explains disparities among case studies, and stakes out critical baseline expectations for regional management efforts. We also reveal clear multi‐decadal state shifts on coral reefs: over time, systems dominated by reef‐building corals and small‐bodied, planktivorous fishes tend to have been replaced with reefs characterised by algae and larger‐bodied fishes. Main Conclusions Our results suggest a previously unrecognised transition from systems that harness external subsidies through small‐bodied consumers associated with structurally complex live corals, to herbivore‐dominated systems with stronger bottom‐up dynamics. Overall, the partitioning of complex reef ecosystems into a small suite of discrete ecological states suggests that spatial context‐dependency, shifting baselines and changes in reef functioning are crucial considerations for coral reef management in the 21st century.

Validating costly protected area restoration after (increasing) disasters - Adam Loch; Glen Scholz; David Adamson; Stuart Sexton; Alexandra Peralta (Journal of Environmental Management, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

Chemically induced phenotype plasticity in the unicellular zygnematophyte, Penium margaritaceum - Josephine G. LoRicco; Kaylee Bagdan; Gabriel Sgambettera; Stuart Malone; Tawn Tomasi; Iris Lu; David S. Domozych (Protoplasma, 2024)
Phenotypic plasticity allows a plant cell to alter its structure and function in response to external pressure. This adaptive phenomenon has also been important in the evolution of plants including the emergence of land plants from a streptophyte alga. Penium margaritaceum is a unicellular zygnematophyte (i.e., the group of streptophyte algae that is sister to land plants) that was employed in order to study phenotypic plasticity with a focus on the role of subcellular expansion centers and the cell wall in this process. Live cell fluorescence labeling, immunofluorescence labeling, transmission electron microscopy, and scanning electron microscopy showed significant subcellular changes and alterations to the cell wall. When treated with the actin-perturbing agent, cytochalasin E, cytokinesis is arrested and cells are transformed into pseudo-filaments made of up to eight or more cellular units. When treated with the cyclin-dependent kinase (CDK) inhibitor, roscovitine, cells converted to a unique phenotype with a narrow isthmus zone.

Large-scale serial replacement of invasive tench (Tinca tinca) by invasive carp (Cyprinus carpio) in the presence of redfin perch (Perca fluviatilis) in the Murray-Darling River system, Australia - Matthew P. Hill; Peter Caley; Ivor Stuart; Richard P. Duncan; David M. Forsyth (Biological Invasions, 2024)
Ecosystems worldwide are increasingly being invaded by multiple species, and the rate of biological invasion is accelerating, leading to more interactions among invasive species. One such interaction that has received little attention is the phenomenon of ‘serial replacement’ or ‘over-invasion’, where an established invasive species is supplanted by a second invasive species. Understanding this interaction is important as controlling the second species could inadvertently lead to an increase in the abundance of the first species. We used a hierarchical state-space model to analyse changes in annual abundances (commercial catch-per-unit-effort) of three invasive fish species, tench ( Tinca tinca ), common carp ( Cyprinus carpio ) and redfin perch ( Perca fluviatilis ), in the Murray-Darling River system (MDRS), Australia between 1954–2002. Tench were present at low abundances until the mid-1970 s, before declining to the point of no commercial catch post-1989. This rapid decline coincided with a significant increase in carp abundance, suggesting that carp may have driven the tench decline through habitat modification (particularly the destruction of aquatic plants), consistent with findings from European studies that show the disappearance of tench from ponds with intensive carp farming. Redfin perch populations, were inferred to be much less impacted by the invading carp population. While carp were present in the MDRS for the duration of the study, the rapid increase in carp abundance in the early 1970 s coincided with the introduction of a specific genetic lineage—the “Boolarra strain”. Our analysis provides compelling evidence of serial replacement of long-established tench by invading common carp triggered by the introduction of a novel carp strain.

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Artificial light and cloud cover interact to disrupt celestial migrations at night - Leo M. Burke; Thomas W. Davies; David Wilcockson; Stuart Jenkins; Amy Ellison (Science of The Total Environment, 2024)

The new kid on the block in insect pest management: sprayable RNAi goes commercial - Junjie Yan; Ralf Nauen; Stuart Reitz; Andrei Alyokhin; Jiang Zhang; David Mota-Sanchez; Yonggyun Kim; Subba Reddy Palli; Silvia I. Rondon; Brian A. Nault; Juan Luis Jurat-Fuentes; Michael S. Crossley; et al. (Science China Life Sciences, 2024)

Temporal variation in the incidence of seaweed health problems affecting farmed Kappaphycus striatus in relation to environmental conditions in shallow waters - Joseph P. Faisan; Rema C. Sibonga; Jonalyn P. Mateo; Maria Rovilla J. Luhan; Victor Marco Emmanuel N. Ferriols; Vicente T. Balinas; Janina Brakel; David Bass; Stuart Ross; Grant D. Stentiford; Juliet Brodie; Georgia M. Ward; et al. (Journal of Applied Phycology, 2024)

Epichloë – a key element of New Zealand’s agricultural landscape - Stuart D. Card; Daniel A. Bastías; Wei Zhang; David E. Hume; John R. Caradus (New Zealand Journal of Botany, 2024)

Review of trace organic chemicals in urban stormwater: Concentrations, distributions, risks, and drivers - Kefeng Zhang; Zhaozhi Zheng; Lena Mutzner; Baiqian Shi; David McCarthy; Pierre Le-Clech; Stuart Khan; Tim D. Fletcher; Marty Hancock; Ana Deletic (Water Research, 2024)

Accelerator mass spectrometry measurements of 233U in groundwater, soil and vegetation at a legacy radioactive waste site - Timothy E. Payne; Jennifer J. Harrison; David P. Child; Stuart Hankin; Michael A.C. Hotchkis; Catherine E. Hughes; Mathew P. Johansen; Sangeeth Thiruvoth; Kerry L. Wilsher (Chemosphere, 2024)

Leveraging wastewater surveillance to detect viral diseases in livestock settings - Warish Ahmed; Yawen Liu; Wendy Smith; Wayne Ingall; Michael Belby; Aaron Bivins; Paul Bertsch; David T. Williams; Kirsty Richards; Stuart Simpson (Science of The Total Environment, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Factors influencing migration of short‐finned eels ( Anguilla australis ) over 3 years from a wetland system, Lake Condah, south‐east Australia, downstream to the sea - Wayne Koster; Ben Church; David Crook; David Dawson; Ben Fanson; Justin O'Connor; Ivor Stuart (Journal of Fish Biology, 2024)
Anguillid eel populations are under threat globally. A particularly vulnerable life‐cycle stage is the migration of mature adult eels downstream from freshwater habitats through estuaries into the sea to spawn. This study investigated the factors associated with downstream migration of the short‐finned eel Anguilla australis (Richardson 1841) from a coastal wetland (Lake Condah) in south‐east Australia, using acoustic telemetry. Migration was associated with time of the year, higher water level and river flows, decreasing water temperature, and darker moon phases. Larger individuals and those in better condition were more likely to migrate from the wetland. Downstream migration peaked in spring, in contrast to the typical autumn migration period for other temperate anguillids. Variable responses, in comparison to other studies, highlight how migration cues may not be universal. In south‐east Australia, short‐finned eels may have evolved to migrate in multiple phases by first migrating to the estuary during typical seasonal spring flow pulses (e.g., to avoid being stranded in upland reaches during dry summer periods) and then migrating into the ocean in autumn. More research is needed to unravel these processes and causes, especially considering that the relationship between migration and hydrology may be complex and confounded (e.g., by human‐induced disruptions to migratory pathways).

Predicting recreational water quality and public health safety in urban estuaries using Bayesian Networks - Simon D. Lloyd; Guido Carvajal; Meredith Campey; Nerida Taylor; Paul Osmond; David J. Roser; Stuart J. Khan (Water Research, 2024)

Mass spectrometry-based metabolomics for the elucidation of alkaloid biosynthesis and function in invasive Vincetoxicum rossicum populations - Christine J. Kempthorne; Max St. Pierre; Andrew Le; Stuart Livingstone; James McNulty; Marc W. Cadotte; David K. Liscombe (Phytochemistry, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

Rarity mediates species‐specific responses of tropical reef fishes to protection - Loïc Sanchez; Nicolas Loiseau; Graham J. Edgar; Cyril Hautecoeur; Fabien Leprieur; Stéphanie Manel; Matthew McLean; Rick D. Stuart‐Smith; Laure Velez; David Mouillot (Ecology Letters, 2024)
Marine protected areas (MPAs) are the most widely applied tool for marine biodiversity conservation, yet many gaps remain in our understanding of their species‐specific effects, partly because the socio‐environmental context and spatial autocorrelation may blur and bias perceived conservation outcomes. Based on a large data set of nearly 3000 marine fish surveys spanning all tropical regions of the world, we build spatially explicit models for 658 fish species to estimate species‐specific responses to protection while controlling for the environmental, habitat and socio‐economic contexts experienced across their geographic ranges. We show that the species responses are highly variable, with ~40% of fishes not benefitting from protection. When investigating how traits influence species' responses, we find that rare top‐predators and small herbivores benefit the most from MPAs while mid‐trophic level species benefit to a lesser extent, and rare large herbivores experience adverse effects, indicating potential trophic cascades.

Concentrations and legislative aspects of PBDEs in plastic of waste electrical and electronic equipment in Brazil - Hansel David Burgos Melo; Juliana de Souza-Araujo; Laura Geraldine Benavides Garzón; João Carlos Macedo; Rafael Cardoso; Sandro Donnini Mancini; Stuart Harrad; André Henrique Rosa (Science of The Total Environment, 2024)

Forecasting a Summer of Extremes: Building Stakeholder Response Capacity to Marine Heatwaves - Alistair Hobday; Claire Spillman; Jamie Allnutt; Melinda Coleman; Fred Bailleul; Laura Blamey; Stephanie Brodie; Arani Chandrapavan; Jason Hartog; David Maynard; Craig Mundy; Eva Plaganyi; et al. (Oceanography, 2024)
Forecasts of an El Niño in 2023/2024 raised concern among Australian marine stakeholders regarding its potential impacts on marine industries and systems. National level seafood-focused climate briefings were requested by the fisheries sector for the first time, driven by various state and regional level meetings and information requests. To respond to stakeholder needs, six virtual national marine climate briefings were undertaken through the austral 2023/2024 summer, underpinned by new subseasonal to seasonal marine heatwave forecast capabilities. These briefings were developed in collaboration with multiple science organizations and were targeted to industry and management authorities across the Australian seafood sector. As a result, targeted information products, additional regional and sector-specific briefings, and state response plans were developed. Collectively, these briefings were a catalyst for positive and rapid action in policy, management, industry, and research arenas. This experience showed that the combination of seasonal forecasting capability, inter-agency coordination, strong stakeholder engagement, and effective science communication plays a critical role in improving the understanding of, planning for, and responses to extreme events.

Interrelationships and biogeography of the New World pufferfish genus Sphoeroides (Tetraodontiformes: Tetraodontidae) inferred using ultra-conserved DNA elements - Elizabeth P. Hunt; Stuart C. Willis; Kevin W. Conway; David S. Portnoy (Molecular Phylogenetics and Evolution, 2023)

Improving toxicity prediction of metal-contaminated sediments by incorporating sediment properties - Yanfeng Zhang; Minwei Xie; David M. Spadaro; Stuart L. Simpson (Environmental Pollution, 2023)

Effects of management objectives and rules on marine conservation outcomes - Natalie C. Ban; Emily S. Darling; Georgina G. Gurney; Whitney Friedman; Stacy D. Jupiter; W. Peni Lestari; Irfan Yulianto; Sinta Pardede; Sukma A. R. Tarigan; Puji Prihatiningsih; Sangeeta Mangubhai; Waisea Naisilisili; et al. (Conservation Biology, 2023)
Understanding the relative effectiveness and enabling conditions of different area‐based management tools is essential for supporting efforts that achieve positive biodiversity outcomes as area‐based conservation coverage increases to meet newly set international targets. We used data from a coastal social–ecological monitoring program in 6 Indo‐Pacific countries to analyze whether social, ecological, and economic objectives and specific management rules (temporal closures, fishing gear‐specific, species‐specific restrictions) were associated with coral reef fish biomass above sustainable yield levels across different types of area‐based management tools (i.e., comparing those designated as marine protected areas [MPAs] with other types of area‐based management). All categories of objectives, multiple combinations of rules, and all types of area‐based management had some sites that were able to sustain high levels of reef fish biomass—a key measure for coral reef functioning—compared with reference sites with no area‐based management. Yet, the same management types also had sites with low biomass. As governments advance their commitments to the Kunming–Montreal Global Biodiversity Framework and the target to conserve 30% of the planet's land and oceans by 2030, we found that although different types of management can be effective, most of the managed areas in our study regions did not meet criteria for effectiveness. These findings underscore the importance of strong management and governance of managed areas and the need to measure the ecological impact of area‐based management rather than counting areas because of their designation.

Occurrence, source apportionment, and ecological risk assessment of organophosphate esters in surface sediment from the Ogun and Osun Rivers, Southwest Nigeria - Muideen Remilekun Gbadamosi; Adeyemi Lawrence Ogunneye; David Olaoluwa Jegede; Mohamed Abou-Elwafa Abdallah; Stuart Harrad (Environmental Science and Pollution Research, 2023)
Organophosphate esters (OPEs) are synthetic chemicals widely used as e.g., flame retardants and plasticisers in various consumer products. Due to the toxicity of OPEs in aquatic ecosystems, exposure of fauna and flora to these compounds is of potential concern. In this study, the concentrations, profiles, sources, and ecological risk of eight OPEs were investigated in the sediments from the two major rivers in southwest Nigeria. Concentrations of ∑OPEs in surface sediments were in the range 13.1 – 2110 ng/g dry weight (dw) (median: 378 ng/g dw) in the Ogun River and 24.7—589 ng/g dw (median: 174 ng/g dw) in the Osun River. These concentrations are broadly within the range of those reported in surface sediment in previous studies conducted in other locations around the world. Tris (2-butoxyethyl) phosphate (TBOEP) was the dominant OPE in the sediment samples with a median concentration of 337 and 126 ng/g dw for the Ogun and Osun Rivers respectively, while tri-n-butyl phosphate (TnBP) was not detected in any sample. Excluding TBOEP, the chlorinated organophosphate esters: tris(2-chloroethyl) phosphate (TCEP), tris(2-chloro-propyl) phosphate (TCIPP), and tris(1,3-dichloro-2-propyl) phosphate (TDCIPP) were the dominant OPEs in the Osun River, while the aryl-OPEs: triphenyl phosphate (TPHP), 2-ethylhexyl diphenyl phosphate (EHDPP), and tri- m -tolyl phosphate (TMTP) were dominant in the Ogun River. Under a median exposure scenario, moderate ecological risk was predicted from exposure to TCIPP in the Osun River. In contrast, under a high exposure scenario, concentrations of TDCIPP (risk quotient, RQ = 5.33—5.37) constituted a high ecological risk in both rivers, with moderate risks observed for TBOEP (RQ = 0.022—0.18) and TCIPP (RQ = 0.097 – 0.16). Therefore, the risk to aquatic organisms from concomitant exposure to mixtures of OPEs in freshwater ecosystems requires further investigation. Graphical Abstract

Distribution transforms for guiding center orbit coordinates in axisymmetric tokamak equilibria - Stuart Benjamin; Henrik Järleblad; Mirko Salewski; Luke Stagner; Matthew Hole; David Pfefferlé (Computer Physics Communications, 2023)

Continuous home cage monitoring of activity and sleep in mice during repeated paroxetine treatment and discontinuation - Helen M. Collins; Raquel Pinacho; S. K. Eric Tam; Trevor Sharp; David M. Bannerman; Stuart N. Peirson (Psychopharmacology, 2023)
Rationale Non-invasive home cage monitoring is emerging as a valuable tool to assess the effects of experimental interventions on mouse behaviour. A field in which these techniques may prove useful is the study of repeated selective serotonin reuptake inhibitor (SSRI) treatment and discontinuation. SSRI discontinuation syndrome is an under-researched condition that includes the emergence of sleep disturbances following treatment cessation. Objectives We used passive infrared (PIR) monitoring to investigate changes in activity, sleep, and circadian rhythms during repeated treatment with the SSRI paroxetine and its discontinuation in mice. Methods Male mice received paroxetine (10 mg/kg/day, s.c. ) for 12 days, then were swapped to saline injections for a 13 day discontinuation period and compared to mice that received saline injections throughout. Mice were continuously tracked using the Continuous Open Mouse Phenotyping of Activity and Sleep Status (COMPASS) system. Results Repeated paroxetine treatment reduced activity and increased behaviourally-defined sleep in the dark phase. These effects recovered to saline-control levels within 24 h of paroxetine cessation, yet there was also evidence of a lengthening of sleep bouts in the dark phase for up to a week following discontinuation. Conclusions This study provides the first example of how continuous non-invasive home cage monitoring can be used to detect objective behavioural changes in activity and sleep during and after drug treatment in mice. These data suggest that effects of paroxetine administration reversed soon after its discontinuation but identified an emergent change in sleep bout duration, which could be used as a biomarker in future preclinical studies to prevent or minimise SSRI discontinuation symptoms.

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Seeing the wood for the trees, irregular silviculture supports bat populations in conifer plantations - Patrick Cook; Daniel Alder; Lisbeth Hordley; Stuart E. Newson; David Pengelly (Forest Ecology and Management, 2023)

KRILLPODYM: a mechanistic, spatially resolved model of Antarctic krill distribution and abundance - David B. Green; Olivier Titaud; Sophie Bestley; Stuart P. Corney; Mark A. Hindell; Rowan Trebilco; Anna Conchon; Patrick Lehodey (Frontiers in Marine Science, 2023)
Robust prediction of population responses to changing environments requires the integration of factors controlling population dynamics with processes affecting distribution. This is true everywhere but especially in polar pelagic environments. Biological cycles for many polar species are synchronised to extreme seasonality, while their distributions may be influenced by both the prevailing oceanic circulation and sea-ice distribution. Antarctic krill (krill, Euphausia superba ) is one such species exhibiting a complex life history that is finely tuned to the extreme seasonality of the Southern Ocean. Dependencies on the timing of optimal seasonal conditions have led to concerns over the effects of future climate on krill’s population status, particularly given the species’ important role within Southern Ocean ecosystems. Under a changing climate, established correlations between environment and species may breakdown. Developing the capacity for predicting krill responses to climate change therefore requires methods that can explicitly consider the interplay between life history, biological conditions, and transport. The Spatial Ecosystem And Population Dynamics Model (SEAPODYM) is one such framework that integrates population and general circulation modelling to simulate the spatial dynamics of key organisms. Here, we describe a modification to SEAPODYM, creating a novel model – KRILLPODYM – that generates spatially resolved estimates of krill biomass and demographics. This new model consists of three major components: (1) an age-structured population consisting of five key life stages, each with multiple age classes, which undergo age-dependent growth and mortality, (2) six key habitats that mediate the production of larvae and life stage survival, and (3) spatial dynamics driven by both the underlying circulation of ocean currents and advection of sea-ice. We present the first results of KRILLPODYM, using published deterministic functions of population processes and habitat suitability rules. Initialising from a non-informative uniform density across the Southern Ocean our model independently develops a circumpolar population distribution of krill that approximates observations. The model framework lends itself to applied experiments aimed at resolving key population parameters, life-stage specific habitat requirements, and dominant transport regimes, ultimately informing sustainable fishery management.

Entry fees enhance marine protected area management and outcomes - Chris Brown; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Nur Arafeh-Dalmau; Christina A. Buelow; Max D. Campbell; Graham J. Edgar; Jonas Geldmann; David Gill; Rick D. Stuart-Smith (Biological Conservation, 2023)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Damage to living trees contributes to almost half of the biomass losses in tropical forests - Daniel Zuleta; Gabriel Arellano; Sean M. McMahon; Salomón Aguilar; Sarayudh Bunyavejchewin; Nicolas Castaño; Chia‐Hao Chang‐Yang; Alvaro Duque; David Mitre; Musalmah Nasardin; Rolando Pérez; I‐Fang Sun; et al. (Global Change Biology, 2023)
Accurate estimates of forest biomass stocks and fluxes are needed to quantify global carbon budgets and assess the response of forests to climate change. However, most forest inventories consider tree mortality as the only aboveground biomass (AGB) loss without accounting for losses via damage to living trees: branchfall, trunk breakage, and wood decay. Here, we use ~151,000 annual records of tree survival and structural completeness to compare AGB loss via damage to living trees to total AGB loss (mortality + damage) in seven tropical forests widely distributed across environmental conditions. We find that 42% (3.62 Mg ha −1 year −1 ; 95% confidence interval [CI] 2.36–5.25) of total AGB loss (8.72 Mg ha −1 year −1 ; CI 5.57–12.86) is due to damage to living trees. Total AGB loss was highly variable among forests, but these differences were mainly caused by site variability in damage‐related AGB losses rather than by mortality‐related AGB losses. We show that conventional forest inventories overestimate stand‐level AGB stocks by 4% (1%–17% range across forests) because assume structurally complete trees, underestimate total AGB loss by 29% (6%–57% range across forests) due to overlooked damage‐related AGB losses, and overestimate AGB loss via mortality by 22% (7%–80% range across forests) because of the assumption that trees are undamaged before dying. Our results indicate that forest carbon fluxes are higher than previously thought. Damage on living trees is an underappreciated component of the forest carbon cycle that is likely to become even more important as the frequency and severity of forest disturbances increase.

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

A global assessment of the prevalence of current and potential future infrastructure in Key Biodiversity Areas - Ashley T. Simkins; Alison E. Beresford; Graeme M. Buchanan; Olivia Crowe; Wendy Elliott; Pablo Izquierdo; David J. Patterson; Stuart H.M. Butchart (Biological Conservation, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Evaluation of Nasal Oxygen Administration at Various Flow Rates and Concentrations in Conscious, Standing Adult Horses - Danielle Gordon; Stuart Clark-Price; Stephanie Keating; David J. Schaeffer; Kara M. Lascola (Journal of Equine Veterinary Science, 2023)

Sialoadhesin (CD169/Siglec-1) is an extended molecule that escapes inhibitory cis-interactions and synergizes with other macrophage receptors to promote phagocytosis - Mariliis Klaas; Stuart Dubock; David J. P. Ferguson; Paul R. Crocker (Glycoconjugate Journal, 2023)
Sialoadhesin (CD169/Siglec-1, Sn) is a macrophage receptor that interacts with sialic acids on both host cells and pathogens. It is a type 1 membrane protein with an unusually large number of 17 extracellular immunoglobulin (Ig)-like domains, made up of an N-terminal V-set domain that binds sialic acid and 16 adjacent C2-set domains. The potential importance of 17 Ig domains in Sn for mediating cellular interactions has not been investigated experimentally. In the present study, Chinese Hamster Ovary (CHO) cells were stably transfected with full-length or truncated forms of Sn. Using human red blood cells (RBC) as a model system, CHO cells expressing truncated forms of Sn with 4 or less Ig domains were unable to bind RBC in comparison to the full-length protein. Immunoelectron microscopy of the CHO cells indicated that full-length Sn extends ~ 33 nm from the plasma membrane compared with ~ 14 nm for a truncated form with 6 N-terminal Ig domains. Co-expresssion of Sn-expressing CHO cells with heavily glycosylated membrane proteins of differing predicted lengths resulted in selective modulation of Sn-dependent binding to RBC and supported the hypothesis that Sn has evolved 17 Ig domains to escape inhibitory cis -interactions. The functional significance of the extended length of Sn was demonstrated in experiments with macrophages showing that Sn synergizes with phagocytic receptors FcR and TIM-4 to strongly promote uptake of IgG-opsonized and eryptotic RBC respectively.

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

A two phase escarpment evolution of the Red Sea margin of southwestern Saudi Arabia. Insights from low-temperature apatite thermochronology - Syed Ali Turab; Kurt Stüwe; Finlay M. Stuart; Nathan Cogne; David M. Chew; Jörg Robl (Earth and Planetary Science Letters, 2023)

Introducing a common taxonomy to support learning from failure in conservation - Iain Dickson; Stuart H. M. Butchart; Allison Catalano; David Gibbons; Julia P. G. Jones; Katie Lee‐Brooks; Thomasina Oldfield; David Noble; Stuart Paterson; Sugoto Roy; Julien Semelin; Paul Tinsley‐Marshall; et al. (Conservation Biology, 2023)
Although some sectors have made significant progress in learning from failure, there is currently limited consensus on how a similar transition could best be achieved in conservation and what is required to facilitate this. One of the key enabling conditions for other sectors is a widely accepted and standardized classification system for identifying and analyzing root causes of failure. We devised a comprehensive taxonomy of root causes of failure affecting conservation projects. To develop this, we solicited examples of real‐life conservation efforts that were deemed to have failed in some way, identified their underlying root causes of failure, and used these to develop a generic, 3‐tier taxonomy of the ways in which projects fail, at the top of which are 6 overarching cause categories that are further divided into midlevel cause categories and specific root causes. We tested the taxonomy by asking conservation practitioners to use it to classify the causes of failure for conservation efforts they had been involved in. No significant gaps or redundancies were identified during this testing phase. We then analyzed the frequency that particular root causes were encountered by projects within this test sample, which suggested that some root causes were more likely to be encountered than others and that a small number of root causes were more likely to be encountered by projects implementing particular types of conservation action. Our taxonomy could be used to improve identification, analysis, and subsequent learning from failed conservation efforts, address some of the barriers that currently limit the ability of conservation practitioners to learn from failure, and contribute to establishing an effective culture of learning from failure within conservation.

IP3R activity increases propensity of RyR-mediated sparks by elevating dyadic [Ca2＋] - Joshua Chung; Agnė Tilūnaitė; David Ladd; Hilary Hunt; Christian Soeller; Edmund J. Crampin; Stuart T. Johnston; H. Llewelyn Roderick; Vijay Rajagopal (Mathematical Biosciences, 2023)

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

De novo mutations in the BMP signaling pathway in lambdoid craniosynostosis - Andrew T. Timberlake; Emre Kiziltug; Sheng Chih Jin; Carol Nelson-Williams; Erin Loring; August Allocco; Arnaud Marlier; Siddharth Banka; Helen Stuart; Maria Rita Passos-Buenos; Rafael Rosa; Silvia R. Rogatto; et al. (Human Genetics, 2023)

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

Spatiotemporal influences of climate and humans on muskox range dynamics over multiple millennia - Elisabetta Canteri; Stuart C. Brown; Niels Martin Schmidt; Rasmus Heller; David Nogués‐Bravo; Damien A. Fordham (Global Change Biology, 2022)
Processes leading to range contractions and population declines of Arctic megafauna during the late Pleistocene and early Holocene are uncertain, with intense debate on the roles of human hunting, climatic change, and their synergy. Obstacles to a resolution have included an overreliance on correlative rather than process‐explicit approaches for inferring drivers of distributional and demographic change. Here, we disentangle the ecological mechanisms and threats that were integral in the decline and extinction of the muskox ( Ovibos moschatus ) in Eurasia and in its expansion in North America using process‐explicit macroecological models. The approach integrates modern and fossil occurrence records, ancient DNA, spatiotemporal reconstructions of past climatic change, species‐specific population ecology, and the growth and spread of anatomically modern humans. We show that accurately reconstructing inferences of past demographic changes for muskox over the last 21,000 years require high dispersal abilities, large maximum densities, and a small Allee effect. Analyses of validated process‐explicit projections indicate that climatic change was the primary driver of muskox distribution shifts and demographic changes across its previously extensive (circumpolar) range, with populations responding negatively to rapid warming events. Regional analyses show that the range collapse and extinction of the muskox in Europe (~13,000 years ago) was likely caused by humans operating in synergy with climatic warming. In Canada and Greenland, climatic change and human activities probably combined to drive recent population sizes. The impact of past climatic change on the range and extinction dynamics of muskox during the Pleistocene–Holocene transition signals a vulnerability of this species to future increased warming. By better establishing the ecological processes that shaped the distribution of the muskox through space and time, we show that process‐explicit macroecological models have important applications for the future conservation and management of this iconic species in a warming Arctic.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Tree crown damage and its effects on forest carbon cycling in a tropical forest - Jessica F. Needham; Gabriel Arellano; Stuart J. Davies; Rosie A. Fisher; Valerie Hammer; Ryan G. Knox; David Mitre; Helene C. Muller‐Landau; Daniel Zuleta; Charlie D. Koven (Global Change Biology, 2022)
Crown damage can account for over 23% of canopy biomass turnover in tropical forests and is a strong predictor of tree mortality; yet, it is not typically represented in vegetation models. We incorporate crown damage into the Functionally Assembled Terrestrial Ecosystem Simulator (FATES), to evaluate how lags between damage and tree recovery or death alter demographic rates and patterns of carbon turnover. We represent crown damage as a reduction in a tree's crown area and leaf and branch biomass, and allow associated variation in the ratio of aboveground to belowground plant tissue. We compare simulations with crown damage to simulations with equivalent instant increases in mortality and benchmark results against data from Barro Colorado Island (BCI), Panama. In FATES, crown damage causes decreases in growth rates that match observations from BCI. Crown damage leads to increases in carbon starvation mortality in FATES, but only in configurations with high root respiration and decreases in carbon storage following damage. Crown damage also alters competitive dynamics, as plant functional types that can recover from crown damage outcompete those that cannot. This is a first exploration of the trade‐off between the additional complexity of the novel crown damage module and improved predictive capabilities. At BCI, a tropical forest that does not experience high levels of disturbance, both the crown damage simulations and simulations with equivalent increases in mortality does a reasonable job of capturing observations. The crown damage module provides functionality for exploring dynamics in forests with more extreme disturbances such as cyclones and for capturing the synergistic effects of disturbances that overlap in space and time.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Gill transcriptome of the yellow peacock bass (Cichla ocellaris monoculus) exposed to contrasting physicochemical conditions - Stuart C. Willis; David E. Saenz; Gang Wang; Christopher M. Hollenbeck; David S. Portnoy; James J. Cai; Kirk O. Winemiller (Conservation Genetics Resources, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic recruitment patterns are patchy and spatiotemporally unpredictable in a deep-water snapper (Lutjanus vivanus) sampled in fished and protected areas of western Puerto Rico - Stuart C. Willis; Christopher M. Hollenbeck; Jonathan B. Puritz; David S. Portnoy (Conservation Genetics, 2022)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Correction to: In Vitro Oxidative Crosslinking of Recombinant Barnacle Cyprid Cement Gland Proteins - Robert Cleverley; David Webb; Stuart Middlemiss; Phillip Duke; Anthony Clare; Keiju Okano; Colin Harwood; Nick Aldred (Marine Biotechnology, 2022)

Differentiating between viruses and virus species by writing their names correctly - Francisco Murilo Zerbini; Stuart G. Siddell; Arcady R. Mushegian; Peter J. Walker; Elliot J. Lefkowitz; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Bas E. Dutilh; María Laura García; Sandra Junglen; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2022)

Learning Together for and with the Martuwarra Fitzroy River - Rosemary Hill; Pia Harkness; Nat Raisbeck-Brown; Ilisapeci Lyons; Jorge G. Álvarez-Romero; Milena Kiatkoski Kim; Dennis Chungalla; Heather Wungundin; Mary Aiken; Jean Malay; Bernadette Williams; Rachel Buissereth; et al. (Sustainability Science, 2022)
Co-production across scientific and Indigenous knowledge systems has become a cornerstone of research to enhance knowledge, practice, ethics, and foster sustainability transformations. However, the profound differences in world views and the complex and contested histories of nation-state colonisation on Indigenous territories, highlight both opportunities and risks for Indigenous people when engaging with knowledge co-production. This paper investigates the conditions under which knowledge co-production can lead to improved Indigenous adaptive environmental planning and management among remote land-attached Indigenous peoples through a case study with ten Traditional Owner groups in the Martuwarra (Fitzroy River) Catchment in Western Australia’s Kimberley region. The research team built a 3D map of the river and used it, together with an interactive table-top projector, to bring together both scientific and Indigenous spatial knowledge. Participatory influence mapping, aligned with Traditional Owner priorities to achieve cultural governance and management planning goals set out in the Fitzroy River Declaration, investigated power relations. An analytical framework, examining underlying mechanisms of social learning, knowledge promotion and enhancing influence, based on different theories of change, was applied to unpack the immediate outcomes from these activities. The analysis identified that knowledge co-production activities improved the accessibility of the knowledge, the experiences of the knowledge users, strengthened collective identity and partnerships, and strengthened Indigenous-led institutions. The focus on cultural governance and management planning goals in the Fitzroy River Declaration enabled the activities to directly affect key drivers of Indigenous adaptive environmental planning and management—the Indigenous-led institutions. The nation-state arrangements also gave some support to local learning and decision-making through a key Indigenous institution, Martuwarra Fitzroy River Council. Knowledge co-production with remote land-attached Indigenous peoples can improve adaptive environmental planning and management where it fosters learning together, is grounded in the Indigenous-led institutions and addresses their priorities.

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Variable vulnerability to climate change in New Zealand lizards - Scott Jarvie; Travis Ingram; David G. Chapple; Rodney A. Hitchmough; Stuart V. Nielsen; Joanne M. Monks (Journal of Biogeography, 2022)
Aim The primary drivers of species and population extirpations have been habitat loss, overexploitation and invasive species, but human‐mediated climate change is expected to be a major driver in future. To minimise biodiversity loss, conservation managers should identify species vulnerable to climate change and prioritise their protection. Here, we estimate climatic suitability for two species‐rich taxonomic groups, then use phylogenetic analyses to assess vulnerability to climate change. Location Aotearoa New Zealand (NZ). Taxa NZ lizards: diplodactylid geckos and eugongylinae skinks. Methods We built correlative species distribution models (SDMs) for NZ geckos and skinks to estimate climatic suitability under current climate and 2070 future climate scenarios. We then used Bayesian phylogenetic mixed models (BPMMs) to assess vulnerability for both groups with predictor variables for life‐history traits (body size and activity phase) and current distribution (elevation and latitude). We explored two scenarios: an unlimited dispersal scenario, where projections track climate, and a no‐dispersal scenario, where projections are restricted to areas currently identified as suitable. Results SDMs projected vulnerability to climate change for most modelled lizards. For species' ranges projected to decline in climatically suitable areas, average decreases were between 42% and 46% for geckos and 33% and 52% for skinks, although area did increase or remain stable for a minority of species. For the no‐dispersal scenario, the average decrease for geckos was 37%–52% and for skinks was 33%–52%. Our BPMMs showed phylogenetic signal in climate change vulnerability for both groups, with elevation increasing vulnerability for geckos, and body size reducing vulnerability for skinks. Main conclusions New Zealand lizards showed variable vulnerability to climate change, with most species' ranges predicted to decrease. For species whose suitable climatic space is projected to disappear from within their current range, managed relocation could be considered to establish populations in regions that will be suitable under future climates.

Combining Statistical Design with Deterministic Modelling to Assess the Effect of Site-Specific Factors on the Extent of Landslides - Vincent Lemiale; Carolyn Huston; Stuart Mead; David L. J. Alexander; Paul W. Cleary; Deepak Adhikary; Gary W. Delaney (Rock Mechanics and Rock Engineering, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Quantification of blue carbon pathways contributing to negative feedback on climate change following glacier retreat in West Antarctic fjords - Nadescha Zwerschke; Chester J. Sands; Alejandro Roman‐Gonzalez; David K. A. Barnes; Alice Guzzi; Stuart Jenkins; Carlos Muñoz‐Ramírez; James Scourse (Global Change Biology, 2022)
Global warming is causing significant losses of marine ice around the polar regions. In Antarctica, the retreat of tidewater glaciers is opening up novel, low‐energy habitats (fjords) that have the potential to provide a negative feedback loop to climate change. These fjords are being colonized by organisms on and within the sediment and act as a sink for particulate matter. So far, blue carbon potential in Antarctic habitats has mainly been estimated using epifaunal megazoobenthos (although some studies have also considered macrozoobenthos). We investigated two further pathways of carbon storage and potential sequestration by measuring the concentration of carbon of infaunal macrozoobenthos and total organic carbon (TOC) deposited in the sediment. We took samples along a temporal gradient since time of last glacier ice cover (1–1000 years) at three fjords along the West Antarctic Peninsula. We tested the hypothesis that seabed carbon standing stock would be mainly driven by time since last glacier covered. However, results showed this to be much more complex. Infauna were highly variable over this temporal gradient and showed similar total mass of carbon standing stock per m 2 as literature estimates of Antarctic epifauna. TOC mass in the sediment, however, was an order of magnitude greater than stocks of infaunal and epifaunal carbon and increased with time since last ice cover. Thus, blue carbon stocks and recent gains around Antarctica are likely much higher than previously estimated as is their negative feedback on climate change.

Cover Image - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; Julia Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)

Process‐explicit models reveal pathway to extinction for woolly mammoth using pattern‐oriented validation - Damien A. Fordham; Stuart C. Brown; H. Reşit Akçakaya; Barry W. Brook; Sean Haythorne; Andrea Manica; Kevin T. Shoemaker; Jeremy J. Austin; Benjamin Blonder; July A. Pilowsky; Carsten Rahbek; David Nogues‐Bravo (Ecology Letters, 2022)
Pathways to extinction start long before the death of the last individual. However, causes of early stage population declines and the susceptibility of small residual populations to extirpation are typically studied in isolation. Using validated process‐explicit models, we disentangle the ecological mechanisms and threats that were integral in the initial decline and later extinction of the woolly mammoth. We show that reconciling ancient DNA data on woolly mammoth population decline with fossil evidence of location and timing of extinction requires process‐explicit models with specific demographic and niche constraints, and a constrained synergy of climatic change and human impacts. Validated models needed humans to hasten climate‐driven population declines by many millennia, and to allow woolly mammoths to persist in mainland Arctic refugia until the mid‐Holocene. Our results show that the role of humans in the extinction dynamics of woolly mammoth began well before the Holocene, exerting lasting effects on the spatial pattern and timing of its range‐wide extinction.

Integrating Biophysical, Socio-Economic and Governance Principles Into Marine Reserve Design and Management in Mexico: From Theory to Practice - Magdalena Précoma-de la Mora; Nathan J. Bennett; Stuart Fulton; Adrian Munguia-Vega; Cristina Lasch-Thaler; Mariana Walther-Mendoza; José Alberto Zepeda-Domínguez; Elena Marie Finkbeiner; Alison L. Green; Alvin Suárez; Amy Hudson Weaver; Ana Luisa R. Figueroa Carranza; et al. (Frontiers in Marine Science, 2021)
Marine conservation design and fisheries management are increasingly integrating biophysical, socio-economic and governance considerations. Integrative approaches are adopted to achieve more effective, equitable, inclusive, and robust marine policies and practices. This paper describes a participatory process to co-produce biophysical, socio-economic, and governance principles to guide the design and management of marine reserves in three regions of Mexico: the Pacific region of the Baja California Peninsula, the Gulf of California, and the Mexican Caribbean. The process of co-producing the principles included convening a coordination team, reviewing the science, convening multi-stakeholder workshops, developing and communicating the principles with key practitioners and policy makers, and supporting uptake and application to policy and practice. Biophysical principles were related to: habitat representation and risk spreading; protecting critical, special and unique areas; incorporating connectivity; allowing time for recovery; adapting to changes in climate and ocean chemistry; and considering threats and opportunities. Socio-economic principles focused on: integrating the social context, local aspirations, and human-environment interactions; considering economic and non-economic uses, promoting an equitable distribution of costs and benefits, and respecting and maintaining cultural identity and diversity. Governance principles prioritized establishing and ensuring legitimacy and institutional continuity; implementing collaborative and adaptive management; and, promoting effective management. The paper also examines early efforts to implement the principles, next steps to promote further uptake and application in Mexico, and lessons learned from the process. Thus it provides insights into a practical process and a set of principles that are valuable to inform marine conservation and fisheries management processes elsewhere.

In Vitro Oxidative Crosslinking of Recombinant Barnacle Cyprid Cement Gland Proteins - Robert Cleverley; David Webb; Stuart Middlemiss; Phillip Duke; Anthony Clare; Keiju Okano; Colin Harwood; Nick Aldred (Marine Biotechnology, 2021)
Barnacle adhesion is a focus for fouling-control technologies as well as the development of bioinspired adhesives, although the mechanisms remain very poorly understood. The barnacle cypris larva is responsible for surface colonisation. Cyprids release cement from paired glands that contain proteins, carbohydrates and lipids, although further compositional details are scant. Several genes coding for cement gland-specific proteins were identified, but only one of these showed database homology. This was a lysyl oxidase-like protein (lcp_LOX). LOX-like enzymes have been previously identified in the proteome of adult barnacle cement secretory tissue. We attempted to produce recombinant LOX in E. coli , in order to identify its role in cyprid cement polymerisation. We also produced two other cement gland proteins (lcp3_36k_3B8 and lcp2_57k_2F5). lcp2_57k_2F5 contained 56 lysine residues and constituted a plausible substrate for LOX. While significant quantities of soluble lcp3_36k_3B8 and lcp2_57k_2F5 were produced in E. coli , production of stably soluble lcp_LOX failed. A commercially sourced human LOX catalysed the crosslinking of lcp2_57k_2F5 into putative dimers and trimers, and this reaction was inhibited by lcp3_36k_3B8. Inhibition of the lcp_LOX:lcp2_57k_2F5 reaction by lcp3_36k_3B8 appeared to be substrate specific, with no inhibitory effect on the oxidation of cadaverine by LOX. The results demonstrate a possible curing mechanism for barnacle cyprid cement and, thus, provide a basis for a more complete understanding of larval adhesion for targeted control of marine biofouling and adhesives for niche applications.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Climate-Relevant Ocean Transport Measurements in the Atlantic and Arctic Oceans - Barbara Berx; Denis Volkov; Johanna Baehr; Molly Baringer; Peter Brandt; Kristin Burmeister; Stuart Cunningham; Marieke de Jong; Laura de Steur; Shenfu Dong; Eleanor Frajka-Williams; Gustavo Goni; et al. (Oceanography, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

Preliminary survey of pests and diseases of eucheumatoid seaweed farms in the Philippines - Joseph P. Faisan; Ma. Rovilla J. Luhan; Rema C. Sibonga; Jonalyn P. Mateo; Victor Marco Emmanuel N. Ferriols; Janina Brakel; Georgia M. Ward; Stuart Ross; David Bass; Grant D. Stentiford; Juliet Brodie; Anicia Q. Hurtado (Journal of Applied Phycology, 2021)

NET-VISA from Cradle to Adulthood. A Machine-Learning Tool for Seismo-Acoustic Automatic Association - Ronan Le Bras; Nimar Arora; Noriyuki Kushida; Pierrick Mialle; Istvan Bondár; Elena Tomuta; Fekadu Kebede Alamneh; Paulino Feitio; Marcela Villarroel; Beatriz Vera; Alexander Sudakov; Shaban Laban; et al. (Pure and Applied Geophysics, 2021)
A research concept that was first presented on a poster at a Comprehensive Nuclear-Test-Ban Treaty (CTBT) conference in 2009 has resulted in a fully-fledged operational software product named NET-VISA (Network Processing Vertically Integrated Seismic Analysis), which performs the Network Processing step of the automatic processing at the International Data Centre (IDC). It has become one of the tools of the waveform analysts to review and improve the IDC standard automatic third Standard Events List (SEL3) bulletin and produce the Reviewed Events Bulletin (REB), the only global seismo-acoustic bulletin. The basic scientific concepts imbedded into NET-VISA are briefly summarized in this paper but the emphasis is on the process of adopting, developing, adapting, testing, and operationalizing the initial prototype. Extensive off-line testing has shown that one of the expected benefits of NET-VISA was the significant reduction in missed events rate compared to the current Network Processing software, Global Association (GA). NET-VISA also finds some events previously missed by manual review. Starting in July 2017, and as of January 2020, NET-VISA generates an automatic bulletin, called VSEL3, in parallel to SEL3, which is also used by analysts since January 2018. Tracing the origin of the REB events has confirmed the significant reduction in missed events when complementary VSEL3 events are reviewed in addition to the SEL3 events. If sufficient confidence is established, NET-VISA has the potential to replace GA in producing the standard automatic SEL3 bulletin.

New combinations and typifications in Haplopteris (Pteridaceae: Vittarioideae) - Cheng-Wei Chen; Stuart Lindsay; David J. Middleton; Daniele Cicuzza; Eric Schuettpelz (Kew Bulletin, 2021)

Nomenclatural and taxonomic clarifications in Amblovenatum (Thelypteridaceae) - Stuart Lindsay; David J. Middleton (Kew Bulletin, 2021)

Optimizing the application of dairy farm effluent and manure to mitigate gas emission - Obemah David Nartey; Deyan Liu; Jiafa Luo; Stuart Lindsey; Hong J. Di; Zengming Chen; Junji Yuan; Tiehu He; Weixin Ding (Journal of Soils and Sediments, 2021)

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

Coexistence barriers confine the poleward range of a globally distributed plant - David W. Armitage; Stuart E. Jones (Ecology Letters, 2020)
In the study of factors shaping species' poleward range boundaries, climatic constraints are often assigned greater importance than biotic interactions such as competition. However, theory suggests competition can truncate a species' fundamental niche in harsh environments. We test this by challenging a mechanistic niche model – containing explicit competition terms – to predict the poleward range boundaries of two globally distributed, ecologically similar aquatic plant species. Mechanistic competition models accurately predicted the northern range limits of our study species, outperforming competition‐free mechanistic models and matching the predictive ability of statistical niche models fit to occurrence records. Using the framework of modern coexistence theory, we found that relative nonlinearity in competitors' responses to temperature fluctuations maintains their coexistence boundary, highlighting the importance of this fluctuation‐dependent mechanism. Our results support a more nuanced, interactive role of climate and competition in determining range boundaries, and illustrate a practical, process‐based approach to understanding the determinants of range limits.

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Temperature and precipitation at migratory grounds influence demographic trends of an Arctic‐breeding bird - Susan Doyle; David Cabot; Alyn Walsh; Richard Inger; Stuart Bearhop; Barry J. McMahon (Global Change Biology, 2020)
Anthropogenic climate disruption, including temperature and precipitation regime shifts, has been linked to animal population declines since the mid‐20th century. However, some species, such as Arctic‐breeding geese, have thrived during this period. An increased understanding of how climate disruption might link to demographic rates in thriving species is an important perspective in quantifying the impact of anthropogenic climate disruption on the global state of nature. The Greenland barnacle goose ( Branta leucopsis ) population has increased tenfold in abundance since the mid‐20th century. A concurrent weather regime shift towards warmer, wetter conditions occurred throughout its range in Greenland (breeding), Ireland and Scotland (wintering) and Iceland (spring and autumn staging). The aim of this study was to determine the relationship between weather and demographic rates of Greenland barnacle geese to discern the role of climate shifts in the population trend. We quantified the relationship between temperature and precipitation and Greenland barnacle goose survival and productivity over a 50 year period from 1968 to 2018. We detected significant positive relationships between warmer, wetter conditions on the Icelandic spring staging grounds and survival. We also detected contrasting relationships between warmer, wetter conditions during autumn staging and survival and productivity, with warm, dry conditions being the most favourable for productivity. Survival increased in the latter part of the study period, supporting the possibility that spring weather regime shifts contributed to the increasing population trend. This may be related to improved forage resources, as warming air temperatures have been shown to improve survival rates in several other Arctic and northern terrestrial herbivorous species through indirect bottom‐up effects on forage availability.

Controls on Ocean Color Spectra Observed During the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES) - James G. Allen; David A. Siegel; Norman B. Nelson; Stuart Halewood (Frontiers in Marine Science, 2020)

Lessons Learned from Running a Conference in the Time of COVID-19 and the Silver Linings of Shifting to Online - Hannah Power; Madelaine Broadfoot; Annette Burke; Paul Donaldson; Rosanne Hart; Kendall Mollison; David Schmidt; Stuart Young (Oceanography, 2020)

Habitat maps to enhance monitoring and management of the Great Barrier Reef - Chris M. Roelfsema; Eva M. Kovacs; Juan Carlos Ortiz; David P. Callaghan; Karlo Hock; Mathieu Mongin; Kasper Johansen; Peter J. Mumby; Magnus Wettle; Mike Ronan; Petra Lundgren; Emma V. Kennedy; et al. (Coral Reefs, 2020)

Quality and contribution of food sources to Australian lungfish evaluated using fatty acids and stable isotopes - Juan Tao; Mark J. Kennard; David T. Roberts; Brian Fry; Martin J. Kainz; Yifeng Chen; Stuart E. Bunn (Aquatic Sciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Untapped Potential of Citizen Science in Mexican Small-Scale Fisheries - Stuart Fulton; Catalina López-Sagástegui; Amy Hudson Weaver; Fernanda Fitzmaurice-Cahluni; Carlos Galindo; Francisco Fernández-Rivera Melo; Silvia Yee; María Belén Ojeda-Villegas; David Antonio Fuentes; Elizabeth Torres-Bahena (Frontiers in Marine Science, 2019)

Ground Data are Essential for Biomass Remote Sensing Missions - Jérôme Chave; Stuart J. Davies; Oliver L. Phillips; Simon L. Lewis; Plinio Sist; Dmitry Schepaschenko; John Armston; Tim R. Baker; David Coomes; Mathias Disney; Laura Duncanson; Bruno Hérault; et al. (Surveys in Geophysics, 2019)

A genomic assessment of movement and gene flow around the South Florida vicariance zone in the migratory coastal blacknose shark, Carcharhinus acronotus - Pavel V. Dimens; Stuart Willis; R. Dean Grubbs; David S. Portnoy (Marine Biology, 2019)

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

Negative frequency‐dependent growth underlies the stable coexistence of two cosmopolitan aquatic plants - David W. Armitage; Stuart E. Jones (Ecology, 2019)
Identifying and quantifying the mechanisms influencing species coexistence remains a major challenge for the study of community ecology. These mechanisms, which stem from species’ differential responses to competition and their environments, promote coexistence if they give each species a growth advantage when rare. Yet despite the widespread assumption that co‐occurring species stably coexist, there have been few empirical demonstrations in support of this claim. Likewise, coexistence is often assumed to result from interspecific differences in life‐history traits, but the relative contributions of these trait differences to coexistence are rarely quantified, particularly across environmental gradients. Using two widely co‐occurring and ecologically similar species of freshwater duckweed plants ( Spirodela polyrhiza and Lemna minor ), we tested hypotheses that interspecific differences in facultative dormancy behaviors, thermal reaction norms, and density‐dependent growth promote coexistence between these species, and that their relative influences on coexistence change as average temperatures and fluctuations around them vary. In competition experiments, we found strong evidence for negative frequency‐dependent growth across a range of both static and fluctuating temperatures, suggesting a critical role of fluctuation‐independent stabilization in coexistence. This negative frequency dependence could be explained by our observation that for both species, intraspecific competition was over 1.5 times stronger than interspecific competition, granting each species a low‐density growth advantage. Using an empirically parameterized competition model, we found that while coexistence was facilitated by environmental fluctuations, fluctuation‐independent stabilization via negative frequency dependence was crucial for coexistence. Conversely, the temporal storage effect, an important fluctuation‐dependent mechanism, was relatively weak in comparison. Contrary to expectations, differences in the species’ thermal reaction norms and dormancy behaviors did not significantly promote coexistence in fluctuating environments. Our results highlight how coexistence in two ubiquitous and ostensibly similar aquatic plants is not necessarily a product of their most obvious interspecific differences, and instead results from subtle niche differences causing negative frequency‐dependent growth, which acts consistently on both species across environmental gradients.

Long‐term research reveals multiple relationships between the abundance and impacts of a non‐native species - David L. Strayer; Christopher T. Solomon; Stuart E. G. Findlay; Emma J. Rosi (Limnology and Oceanography, 2019)
Non‐native species are among the most important drivers of the structure and function of modern ecosystems. The ecological impacts of a non‐native species ought to depend on the size and characteristics of its population, but the exact nature of this population‐impacts relationship is rarely defined. Both the mathematical form of this relationship (e.g., linear, exponential, and threshold) and the attributes of the invading population (e.g., density, biomass, and body size) that most efficiently describe its impacts could vary greatly across invaders, ecosystems, and ecological variables. Knowing the shape of this relationship could improve management and help to infer mechanisms of interaction between the invader and ecosystem. We used a long‐term data set on the invasion of the Hudson River ecosystem by two species of Dreissena (the zebra mussel, Dreissena polymorpha , and the quagga mussel, Dreissena rostriformis ) to explore the shape of the population‐impacts relationship for selected ecological variables, including seston, phytoplankton, and several taxa of zooplankton. Most population‐impacts relationships appeared to follow a negative exponential form, but we also found apparent thresholds and scatterplots for some variables. Including information on the traits of Dreissena (body size and filtration rate) often substantially improved models of impacts. We found only slight evidence that the resistance of the Hudson River ecosystem to the Dreissena invasion might be increasing over time. Our results suggest important refinements to widely used conceptual models of invasive species impact, and indicate that defining the population‐effects relationship will be essential in understanding and managing the impacts of non‐native species.

Stable increased formulation atomization using a multi-tip nozzle device - Rita Haj-Ahmad; Manoochehr Rasekh; Kazem Nazari; Ekhoerose V. Onaiwu; Bushra Yousef; Stuart Morgan; David Evans; Ming-Wei Chang; John Hall; Chris Samwell; Zeeshan Ahmad (Drug Delivery and Translational Research, 2018)

Lipomyces starkeyi: an emerging cell factory for production of lipids, oleochemicals and biotechnology applications - Bonnie A. McNeil; David T. Stuart (World Journal of Microbiology and Biotechnology, 2018)

Breast Cancer Patients’ Perceptions of a Virtual Learning Environment for Pretreatment Education - Yobelli Alexandra Jimenez; Wei Wang; Kirsty Stuart; Steven Cumming; David Thwaites; Sarah Lewis (Journal of Cancer Education, 2018)

3D human liver tissue from pluripotent stem cells displays stable phenotype in vitro and supports compromised liver function in vivo - Hassan Rashidi; Nguyet-Thin Luu; Salamah M. Alwahsh; Maaria Ginai; Sharmin Alhaque; Hua Dong; Rute A. Tomaz; Bertrand Vernay; Vasanthy Vigneswara; John M. Hallett; Anil Chandrashekran; Anil Dhawan; et al. (Archives of Toxicology, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Seabird Trophic Position Across Three Ocean Regions Tracks Ecosystem Differences - Tyler O. Gagné; K. David Hyrenbach; Molly E. Hagemann; Oron L. Bass; Stuart L. Pimm; Mark MacDonald; Brian Peck; Kyle S. Van Houtan (Frontiers in Marine Science, 2018)

Economic evaluation of micafungin versus liposomal amphotericin B (LAmB) for treating patients with candidaemia and invasive candidiasis (IC) in Turkey - Chin Fen Neoh; Esin Senol; Ates Kara; Ener Cagri Dinleyici; Stuart J. Turner; David C. M. Kong (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

These aren’t the loci you’e looking for: Principles of effective SNP filtering for molecular ecologists - Shannon J. O'Leary; Jonathan B. Puritz; Stuart C. Willis; Christopher M. Hollenbeck; David S. Portnoy (Molecular Ecology, 2018)
Sequencing reduced‐representation libraries of restriction site‐associated DNA ( RAD seq) to identify single nucleotide polymorphisms ( SNP s) is quickly becoming a standard methodology for molecular ecologists. Because of the scale of RAD seq data sets, putative loci cannot be assessed individually, making the process of filtering noise and correctly identifying biologically meaningful signal more difficult. Artefacts introduced during library preparation and/or bioinformatic processing of SNP data can create patterns that are incorrectly interpreted as indicative of population structure or natural selection. Therefore, it is crucial to carefully consider types of errors that may be introduced during laboratory work and data processing, and how to minimize, detect and remove these errors. Here, we discuss issues inherent to RAD seq methodologies that can result in artefacts during library preparation and locus reconstruction resulting in erroneous SNP calls and, ultimately, genotyping error. Further, we describe steps that can be implemented to create a rigorously filtered data set consisting of markers accurately representing independent loci and compare the effect of different combinations of filters on four RAD data sets. At last, we stress the importance of publishing raw sequence data along with final filtered data sets in addition to detailed documentation of filtering steps and quality control measures.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Safety, tolerability and pharmacokinetics of GSK3008348, a novel integrin αvβ6 inhibitor, in healthy participants - Charlotte H. Maden; David Fairman; Michelle Chalker; Maria J. Costa; William A. Fahy; Nadia Garman; Pauline T. Lukey; Tim Mant; Simon Parry; Juliet K. Simpson; Robert J. Slack; Stuart Kendrick; et al. (European Journal of Clinical Pharmacology, 2018)

Ammonia‐oxidizing bacteria are the primary N 2 O producers in an ammonia‐oxidizing archaea dominated alkaline agricultural soil - Kelley A. Meinhardt; Nejc Stopnisek; Manmeet W. Pannu; Stuart E. Strand; Steven C. Fransen; Karen L. Casciotti; David A. Stahl (Environmental Microbiology, 2018)
Summary Most agricultural N 2 O emissions are a consequence of microbial transformations of nitrogen (N) fertilizer, and mitigating increases in N 2 O emission will depend on identifying microbial sources and variables influencing their activities. Here, using controlled microcosm and field studies, we found that synthetic N addition in any tested amount stimulated the production of N 2 O from ammonia‐oxidizing bacteria (AOB), but not archaea (AOA), from a bioenergy crop soil. The activities of these two populations were differentiated by N treatments, with abundance and activity of AOB increasing as nitrate and N 2 O production increased. Moreover, as N 2 O production increased, the isotopic composition of N 2 O was consistent with an AOB source. Relative N 2 O contributions by both populations were quantified using selective inhibitors and varying N availability. Complementary field analyses confirmed a positive correlation between N 2 O flux and AOB abundance with N application. Collectively, our data indicate that AOB are the major N 2 O producers, even with low N addition, and that better‐metered N application, complemented by selective inhibitors, could reduce projected N 2 O emissions from agricultural soils.

Population in vitro–in vivo pharmacokinetic model of first-pass metabolism: itraconazole and hydroxy-itraconazole - Ahmad Y. Abuhelwa; Stuart Mudge; Richard N. Upton; David J. R. Foster (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

The Mekong River: trading off hydropower, fish, and food - Jamie Pittock; David Dumaresq; Stuart Orr (Regional Environmental Change, 2017)

Alien plants as mediators of ecosystem services and disservices in urban systems: a global review - Luke J. Potgieter; Mirijam Gaertner; Christoph Kueffer; Brendon M. H. Larson; Stuart W. Livingstone; Patrick J. O’Farrell; David M. Richardson (Biological Invasions, 2017)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Idiosyncratic responses to climate‐driven forest fragmentation and marine incursions in reed frogs from Central Africa and the Gulf of Guinea Islands - Rayna C. Bell; Juan L. Parra; Gabriel Badjedjea; Michael F. Barej; David C. Blackburn; Marius Burger; Alan Channing; Jonas Maximilian Dehling; Eli Greenbaum; Václav Gvoždík; Jos Kielgast; Chifundera Kusamba; et al. (Molecular Ecology, 2017)
Organismal traits interact with environmental variation to mediate how species respond to shared landscapes. Thus, differences in traits related to dispersal ability or physiological tolerance may result in phylogeographic discordance among co‐distributed taxa, even when they are responding to common barriers. We quantified climatic suitability and stability, and phylogeographic divergence within three reed frog species complexes across the Guineo‐Congolian forests and Gulf of Guinea archipelago of Central Africa to investigate how they responded to a shared climatic and geological history. Our species‐specific estimates of climatic suitability through time are consistent with temporal and spatial heterogeneity in diversification among the species complexes, indicating that differences in ecological breadth may partly explain these idiosyncratic patterns. Likewise, we demonstrated that fluctuating sea levels periodically exposed a land bridge connecting Bioko Island with the mainland Guineo‐Congolian forest and that habitats across the exposed land bridge likely enabled dispersal in some species, but not in others. We did not find evidence that rivers are biogeographic barriers across any of the species complexes. Despite marked differences in the geographic extent of stable climates and temporal estimates of divergence among the species complexes, we recovered a shared pattern of intermittent climatic suitability with recent population connectivity and demographic expansion across the Congo Basin. This pattern supports the hypothesis that genetic exchange across the Congo Basin during humid periods, followed by vicariance during arid periods, has shaped regional diversity. Finally, we identified many distinct lineages among our focal taxa, some of which may reflect incipient or unrecognized species.

Variations of leaf longevity in tropical moist forests predicted by a trait‐driven carbon optimality model - Xiangtao Xu; David Medvigy; Stuart Joseph Wright; Kaoru Kitajima; Jin Wu; Loren P. Albert; Giordane A. Martins; Scott R. Saleska; Stephen W. Pacala (Ecology Letters, 2017)
Leaf longevity ( LL ) varies more than 20‐fold in tropical evergreen forests, but it remains unclear how to capture these variations using predictive models. Current theories of LL that are based on carbon optimisation principles are challenging to quantitatively assess because of uncertainty across species in the ‘ageing rate:’ the rate at which leaf photosynthetic capacity declines with age. Here, we present a meta‐analysis of 49 species across temperate and tropical biomes, demonstrating that the ageing rate of photosynthetic capacity is positively correlated with the mass‐based carboxylation rate of mature leaves. We assess an improved trait‐driven carbon optimality model with in situ LL data for 105 species in two Panamanian forests. We show that our model explains over 40% of the cross‐species variation in LL under contrasting light environment. Collectively, our results reveal how variation in LL emerges from carbon optimisation constrained by both leaf structural traits and abiotic environment.

A complex history of introgression and vicariance in a threatened montane skink (Pseudemoia cryodroma) across an Australian sky island system - Margaret L. Haines; Devi Stuart-Fox; Joanna Sumner; Nick Clemann; David G. Chapple; Jane Melville (Conservation Genetics, 2017)

Quantitative trait loci controlling vegetative propagation traits mapped in European pear (Pyrus communis L.) - Mareike Knäbel; Adam P. Friend; John W. Palmer; Robert Diack; Susan E. Gardiner; Stuart Tustin; Robert Schaffer; Toshi Foster; David Chagné (Tree Genetics & Genomes, 2017)

Climate change as a long-term stressor for the fisheries of the Laurentian Great Lakes of North America - Paris D. Collingsworth; David B. Bunnell; Michael W. Murray; Yu-Chun Kao; Zachary S. Feiner; Randall M. Claramunt; Brent M. Lofgren; Tomas O. Höök; Stuart A. Ludsin (Reviews in Fish Biology and Fisheries, 2017)

The assessment of neuromuscular fatigue during 120 min of simulated soccer exercise - Stuart Goodall; Kevin Thomas; Liam David Harper; Robert Hunter; Paul Parker; Emma Stevenson; Daniel West; Mark Russell; Glyn Howatson (European Journal of Applied Physiology, 2017)

Bioethanol Production from Brewers Spent Grains Using a Fungal Consolidated Bioprocessing (CBP) Approach - Stuart Wilkinson; Katherine A. Smart; Sue James; David J. Cook (BioEnergy Research, 2017)

Does range‐restricted evolutionary history predict extinction risk? A case study in lizards - Giovanni Di Virgilio; Shawn W. Laffan; Stuart V. Nielsen; David G. Chapple (Journal of Biogeography, 2017)
Aim Conservation is often prioritized by identifying regional clusters of threatened or endemic species. Another approach is to assess the evolutionary distinctiveness of groups of taxa using phylodiversity measures. However, quantification of evolutionary history has traditionally not accounted for its uneven geographical distribution due to the variation in species ranges. We assess the efficacy of phylogenetic endemism ( PE ) to predict high extinction risk in comparison to estimates of species range restriction (weighted endemism, WE ) and phylogenetic diversity ( PD ). PE measures the relative range restriction of evolutionary history (lineages), while WE concentrates on the tips of the tree of life, treating all such branches as being of equal length. Location/Methods Using New Zealand's endemic skinks and geckos, we mapped the geographical variation in their extinction risk, PE , WE and PD and measured the extent to which extinction risk exhibited phylogenetic clustering for each group. Correlations between geographical concentrations of high skink and gecko extinction risk with PE , WE and PD were calculated. Results PE was predictive of spatial clusters of high extinction risk for geckos ( r 2 = 0.34, P 0.001) while WE was markedly less so ( r 2 = 0.19, P 0.001). The reverse applied to skinks, with WE most predictive of high risk ( r 2 = 0.26, P 0.001). The phylogenetic signal of extinction risk was significantly conserved for geckos, but was weaker and non‐significant for skinks. PE and WE were not predictive of low risk. PD was not predictive of risk. Main conclusions PE and related measures may be predictive of extinction risk when risk is phylogenetically conserved. Mapping the geographical variation in PE could be a useful first assessment of extinction risk for many groups because phylogenies are increasingly available, while full risk status categories are not. These findings might apply to other groups and locations and warrant further investigation.

UK dietary exposure to PCDD/Fs, PCBs, PBDD/Fs, PBBs and PBDEs: comparison of results from 24-h duplicate diets and total diet studies - Lindsay Bramwell; David Mortimer; Martin Rose; Alwyn Fernandes; Stuart Harrad; Tanja Pless-Mulloli (Food Additives & Contaminants: Part A, 2017)

Nucleus incertus promotes cortical desynchronization and behavioral arousal - Sherie Ma; Giancarlo Allocca; Emma K. E. Ong-Pålsson; Caitlin E. Singleton; David Hawkes; Stuart J. McDougall; Spencer J. Williams; Ross A. D. Bathgate; Andrew L. Gundlach (Brain Structure and Function, 2017)

Determinants of bird conservation‐action implementation and associated population trends of threatened species - David A. Luther; Thomas M. Brooks; Stuart H.M. Butchart; Matt W. Hayward; Marieke E. Kester; John Lamoreux; Amy Upgren (Conservation Biology, 2016)
Conservation actions, such as habitat protection, attempt to halt the loss of threatened species and help their populations recover. The efficiency and the effectiveness of actions have been examined individually. However, conservation actions generally occur simultaneously, so the full suite of implemented conservation actions should be assessed. We used the conservation actions underway for all threatened and near‐threatened birds of the world (International Union for Conservation of Nature Red List of Threatened Species) to assess which biological (related to taxonomy and ecology) and anthropogenic (related to geoeconomics) factors were associated with the implementation of different classes of conservation actions. We also assessed which conservation actions were associated with population increases in the species targeted. Extinction‐risk category was the strongest single predictor of the type of conservation actions implemented, followed by landmass type (continent, oceanic island, etc.) and generation length. Species targeted by invasive nonnative species control or eradication programs, ex situ conservation, international legislation, reintroduction, or education, and awareness‐raising activities were more likely to have increasing populations. These results illustrate the importance of developing a predictive science of conservation actions and the relative benefits of each class of implemented conservation action for threatened and near‐threatened birds worldwide.

Stable isotopes and mtDNA reveal niche segregation but no evidence of intergradation along a habitat gradient in the Lesser Whitethroat complex (Sylvia curruca; Passeriformes; Aves) - Stephen C. Votier; Simon Aspinall; Stuart Bearhop; David Bilton; Jason Newton; Per Alström; Paul Leader; Geoff Carey; Robert W. Furnes; Urban Olsson (Journal of Ornithology, 2016)

Mass‐flowering crops dilute pollinator abundance in agricultural landscapes across Europe - Andrea Holzschuh; Matteo Dainese; Juan P. González‐Varo; Sonja Mudri‐Stojnić; Verena Riedinger; Maj Rundlöf; Jeroen Scheper; Jennifer B. Wickens; Victoria J. Wickens; Riccardo Bommarco; David Kleijn; Simon G. Potts; et al. (Ecology Letters, 2016)
Mass‐flowering crops ( MFC s) are increasingly cultivated and might influence pollinator communities in MFC fields and nearby semi‐natural habitats ( SNH s). Across six European regions and 2 years, we assessed how landscape‐scale cover of MFC s affected pollinator densities in 408 MFC fields and adjacent SNH s. In MFC fields, densities of bumblebees, solitary bees, managed honeybees and hoverflies were negatively related to the cover of MFC s in the landscape. In SNH s, densities of bumblebees declined with increasing cover of MFC s but densities of honeybees increased. The densities of all pollinators were generally unrelated to the cover of SNH s in the landscape. Although MFC fields apparently attracted pollinators from SNH s, in landscapes with large areas of MFC s they became diluted. The resulting lower densities might negatively affect yields of pollinator‐dependent crops and the reproductive success of wild plants. An expansion of MFC s needs to be accompanied by pollinator‐supporting practices in agricultural landscapes.

A population approach to characterise amisulpride pharmacokinetics in older people and Alzheimer’s disease - Suzanne Reeves; Julie Bertrand; Fabrizia D’Antonio; Emma McLachlan; Akshay Nair; Stuart Brownings; Suki Greaves; Alan Smith; David Taylor; Robert Howard (Psychopharmacology, 2016)

Influences of Natural and Anthropogenic Factors and Tidal Restoration on Terrestrial Arthropod Assemblages in West Coast North American Estuarine Wetlands - Aaron T. David; Pascale A. L. Goertler; Stuart H. Munsch; Brittany R. Jones; Charles A. Simenstad; Jason D. Toft; Jeffery R. Cordell; Emily R. Howe; Ayesha Gray; Michael P. Hannam; William Matsubu; Erin E. Morgan (Estuaries and Coasts, 2016)

Population In Vitro-In Vivo Correlation Model Linking Gastrointestinal Transit Time, pH, and Pharmacokinetics: Itraconazole as a Model Drug - Ahmad Y. Abuhelwa; Stuart Mudge; David Hayes; Richard N. Upton; David J. R. Foster (Pharmaceutical Research, 2016)

Should I stay or should I go? Fitness costs and benefits of prolonged parent–offspring and sibling–sibling associations in an Arctic-nesting goose population - Mitch D. Weegman; Stuart Bearhop; Geoff M. Hilton; Alyn J. Walsh; Kaitlin M. Weegman; David J. Hodgson; Anthony David Fox (Oecologia, 2016)

Vegetation of riprapped revetments along the freshwater tidal Hudson River, New York - David L. Strayer; Erik Kiviat; Stuart E. G. Findlay; Nancy Slowik (Aquatic Sciences, 2016)

Choice of baseline climate data impacts projected species' responses to climate change - David J. Baker; Andrew J. Hartley; Stuart H. M. Butchart; Stephen G. Willis (Global Change Biology, 2016)
Climate data created from historic climate observations are integral to most assessments of potential climate change impacts, and frequently comprise the baseline period used to infer species‐climate relationships. They are often also central to downscaling coarse resolution climate simulations from General Circulation Models ( GCM s) to project future climate scenarios at ecologically relevant spatial scales. Uncertainty in these baseline data can be large, particularly where weather observations are sparse and climate dynamics are complex (e.g. over mountainous or coastal regions). Yet, importantly, this uncertainty is almost universally overlooked when assessing potential responses of species to climate change. Here, we assessed the importance of historic baseline climate uncertainty for projections of species' responses to future climate change. We built species distribution models ( SDM s) for 895 African bird species of conservation concern, using six different climate baselines. We projected these models to two future periods (2040–2069, 2070–2099), using downscaled climate projections, and calculated species turnover and changes in species‐specific climate suitability. We found that the choice of baseline climate data constituted an important source of uncertainty in projections of both species turnover and species‐specific climate suitability, often comparable with, or more important than, uncertainty arising from the choice of GCM . Importantly, the relative contribution of these factors to projection uncertainty varied spatially. Moreover, when projecting SDM s to sites of biodiversity importance (Important Bird and Biodiversity Areas), these uncertainties altered site‐level impacts, which could affect conservation prioritization. Our results highlight that projections of species' responses to climate change are sensitive to uncertainty in the baseline climatology. We recommend that this should be considered routinely in such analyses.

Agricultural land usage transforms nitrifier population ecology - Anthony D. Bertagnolli; Dylan McCalmont; Kelley A. Meinhardt; Steven C. Fransen; Stuart Strand; Sally Brown; David A. Stahl (Environmental Microbiology, 2016)
Summary Application of nitrogen fertilizer has altered terrestrial ecosystems. Ammonia is nitrified by ammonia and nitrite‐oxidizing microorganisms, converting ammonia to highly mobile nitrate, contributing to the loss of nitrogen, soil nutrients and production of detrimental nitrogen oxides. Mitigating these costs is of critical importance to a growing bioenergy industry. To resolve the impact of management on nitrifying populations, amplicon sequencing of markers associated with ammonia and nitrite‐oxidizing taxa (ammonia monooxygenase‐ amo A , nitrite oxidoreductase‐ nxr B , respectively) was conducted from long‐term managed and nearby native soils in Eastern Washington, USA . Native nitrifier population structure was altered profoundly by management. The native ammonia‐oxidizing archaeal community (comprised primarily by N itrososphaera sister subclusters 1.1 and 2) was displaced by populations of N itrosopumilus , N itrosotalea and different assemblages of N itrososphaera (subcluster 1.1, and unassociated lineages of N itrososphaera ). A displacement of ammonia‐oxidizing bacterial taxa was associated with management, with native groups of Nitrosospira (cluster 2 related, cluster 3A.2) displaced by N itrosospira clusters 8B and 3A.1. A shift in nitrite‐oxidizing bacteria ( NOB ) was correlated with management, but distribution patterns could not be linked exclusively to management. Dominant nxrB sequences displayed only distant relationships to other NOB isolates and environmental clones.

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Structural Characterisation of Non-Deamidated Acidic Variants of Erwinia chrysanthemi L-asparaginase Using Small-Angle X-ray Scattering and Ion-Mobility Mass Spectrometry - David Gervais; Darryl King; Patrick Kanda; Nicholas Foote; Lucy Elliott; Phillip Brown; Natacha O. Lee; Konstantinos Thalassinos; Claire Pizzey; Robert Rambo; Thomas C. Minshull; Mark J. Dickman; et al. (Pharmaceutical Research, 2015)

Challenges for using quantitative PCR test batteries as a TIE-type approach to identify metal exposure in benthic invertebrates - Sharon E. Hook; Hannah L. Osborn; David A. Spadaro; Stuart L. Simpson (Environmental Science and Pollution Research, 2015)

Evidence for multiple sensory circuits in the brain arising from the respiratory system: an anterograde viral tract tracing study in rodents - Alice E. McGovern; Nicholas Davis-Poynter; Seung-Kwon Yang; David G. Simmons; Michael J. Farrell; Stuart B. Mazzone (Brain Structure and Function, 2015)

Size-assortative mating in simultaneous hermaphrodites: an experimental test and a meta-analysis - Stuart Graham; Elodie Chapuis; Stefania Meconcelli; Nicolas Bonel; Kevin Sartori; Ananda Christophe; Pilar Alda; Patrice David; Tim Janicke (Behavioral Ecology and Sociobiology, 2015)

Combination of herbivore removal and nitrogen deposition increases upland carbon storage - Stuart W. Smith; David Johnson; Samuel L. O. Quin; Kyle Munro; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Global Change Biology, 2015)
Ecosystem carbon (C) accrual and storage can be enhanced by removing large herbivores as well as by the fertilizing effect of atmospheric nitrogen (N) deposition. These drivers are unlikely to operate independently, yet their combined effect on aboveground and belowground C storage remains largely unexplored. We sampled inside and outside 19 upland grazing exclosures, established for up to 80 years, across an N deposition gradient (5–24 kg N ha −1 yr −1 ) and found that herbivore removal increased aboveground plant C stocks, particularly in moss, shrubs and litter. Soil C storage increased with atmospheric N deposition, and this was moderated by the presence or absence of herbivores. In exclosures receiving above 11 kg N ha −1 year −1 , herbivore removal resulted in increased soil C stocks. This effect was typically greater for exclosures dominated by dwarf shrubs ( Calluna vulgaris ) than by grasses ( Molinia caerulea ). The same pattern was observed for ecosystem C storage. We used our data to predict C storage for a scenario of removing all large herbivores from UK heathlands. Predictions were made considering herbivore removal only (ignoring N deposition) and the combined effects of herbivore removal and current N deposition rates. Predictions including N deposition resulted in a smaller increase in UK heathland C storage than predictions using herbivore removal only. This finding was driven by the fact that the majority of UK heathlands receive low N deposition rates at which herbivore removal has little effect on C storage. Our findings demonstrate the crucial link between herbivory by large mammals and atmospheric N deposition, and this interaction needs to be considered in models of biogeochemical cycling.

Contemporary evolution of resistance at the major insecticide target site gene Ace‐1 by mutation and copy number variation in the malaria mosquito Anopheles gambiae - David Weetman; Sara N. Mitchell; Craig S. Wilding; Daniel P. Birks; Alexander E. Yawson; John Essandoh; Henry D. Mawejje; Luc S. Djogbenou; Keith Steen; Emily J. Rippon; Christopher S. Clarkson; Stuart G. Field; et al. (Molecular Ecology, 2015)
Functionally constrained genes are ideal insecticide targets because disruption is often fatal, and resistance mutations are typically costly. Synaptic acetylcholinesterase ( AC hE) is an essential neurotransmission enzyme targeted by insecticides used increasingly in malaria control. In Anopheles and Culex mosquitoes, a glycine–serine substitution at codon 119 of the Ace‐1 gene confers both resistance and fitness costs, especially for 119S/S homozygotes. G119S in Anopheles gambiae from Accra (Ghana) is strongly associated with resistance, and, despite expectations of cost, resistant 119S alleles are increasing significantly in frequency. Sequencing of Accra females detected only a single Ace‐1 119S haplotype, whereas 119G diversity was high overall but very low at non‐synonymous sites, evidence of strong purifying selection driven by functional constraint. Flanking microsatellites showed reduced diversity, elevated linkage disequilibrium and high differentiation of 119S, relative to 119G homozygotes across up to two megabases of the genome. Yet these signals of selection were inconsistent and sometimes weak tens of kilobases from Ace‐1 . This unexpected finding is attributable to apparently ubiquitous amplification of 119S alleles as part of a large copy number variant ( CNV ) far exceeding the size of the Ace‐1 gene, whereas 119G alleles were unduplicated. Ace‐1 CNV was detectable in archived samples collected when the 119S allele was rare in Ghana. Multicopy amplification of resistant alleles has not been observed previously and is likely to underpin the recent increase in 119S frequency. The large CNV compromised localization of the strong selective sweep around Ace‐1 , emphasizing the need to integrate CNV analysis into genome scans for selection.

Dual functions of NME1 in suppression of cell motility and enhancement of genomic stability in melanoma - David M. Kaetzel; Mary K. Leonard; Gemma S. Cook; Marian Novak; Stuart G. Jarrett; Xiuwei Yang; Alexey M. Belkin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

High-temperature structural phase transitions in neighborite: a high-resolution neutron powder diffraction investigation - Kevin S. Knight; G. David Price; John A. Stuart; Ian G. Wood (Physics and Chemistry of Minerals, 2015)

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Effects of form of effluent, season and urease inhibitor on ammonia volatilization from dairy farm effluent applied to pasture - Jie Li; Yuanliang Shi; Jiafa Luo; David Houlbrooke; Stewart Ledgard; Anwar Ghani; Stuart Lindsey (Journal of Soils and Sediments, 2014)

Measurement of Subvisible Particulates in Lyophilised Erwinia chrysanthemi l-asparaginase and Relationship with Clinical Experience - David Gervais; Tim Corn; Andrew Downer; Stuart Smith; Alan Jennings (The AAPS Journal, 2014)

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Performance of an empirical bias‐correction of a high‐resolution climate dataset - James C. Bennett; Michael R. Grose; Stuart P. Corney; Christopher J. White; Gregory K. Holz; Jack J. Katzfey; David A. Post; Nathaniel L. Bindoff (International Journal of Climatology, 2014)
We describe the method and performance of a bias‐correction applied to high‐resolution (˜10 km) simulations from a stretched‐grid Regional Climate Model ( RCM ) over Tasmania, Australia. The bias‐correction is a quantile mapping of empirical cumulative frequency distributions. Corrections are applied at a daily time step to five variables: rainfall, potential evaporation (PE), solar radiation, maximum temperature and minimum temperature. Corrections are calculated independently for each season. We show that quantile mapping of empirical distributions can be highly effective in correcting biases in RCM outputs. Cross‐validation shows biases are effectively reduced across the range of cumulative frequency distributions, with few exceptions. The bias‐correction is not as effective at correcting biases for values at or near zero (e.g. in rainfall simulations), although even here the bias‐correction improves biases evident in the uncorrected simulations. In addition, the bias‐correction improves frequency characteristics of variables such as the number of rain days. We use a detrending technique to apply the bias‐correction to 140‐year time series of RCM variables. We show that the bias‐correction effectively preserves long‐term changes (e.g. to the mean and variance) to variables projected by the uncorrected RCM simulations. Correlations between key variables are also largely preserved, thus the bias‐corrected outputs reflect the dynamics of the underlying RCM . However, the bias‐corrected simulations still exhibit some of the deficiencies of the RCM simulations, e.g. the tendency to underestimate the magnitude and duration of large, multi‐day rain events, and the tendency to underestimate the duration of dry spells. The bias‐corrected simulations for six downscaled GCMs for the A2 and B1 emissions scenarios are available to researchers from http://www.tpac.org.au .

The value of a random sampling design for annual monitoring of national populations of larger British terrestrial mammals - Lucy J. Wright; Stuart E. Newson; David G. Noble (European Journal of Wildlife Research, 2014)

Optimizing Carbon Storage Within a Spatially Heterogeneous Upland Grassland Through Sheep Grazing Management - Stuart W. Smith; Charlotte Vandenberghe; Astley Hastings; David Johnson; Robin J. Pakeman; René van der Wal; Sarah J. Woodin (Ecosystems, 2014)

Oligoamides of 2-amino-5-alkylthiazole 4-carboxylic acids: anti-trypanosomal compounds - Stuart Lang; Abedawn I. Khalaf; David Breen; Judith K. Huggan; Carol J. Clements; Simon P. MacKay; Colin J. Suckling (Medicinal Chemistry Research, 2014)

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

Tsunami inundation in Napier, New Zealand, due to local earthquake sources - Stuart A. Fraser; William L. Power; Xiaoming Wang; Laura M. Wallace; Christof Mueller; David M. Johnston (Natural Hazards, 2014)

The ecology of freshwater wrack along natural and engineered Hudson River shorelines - Cornelia Harris; David L. Strayer; Stuart Findlay (Hydrobiologia, 2014)

Novel perennial ryegrass-Neotyphodium endophyte associations: relationships between seed weight, seedling vigour and endophyte presence - Stuart D. Card; M. Philip Rolston; Catherine Lloyd-West; David E. Hume (Symbiosis, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Periprosthetic osteolysis after total hip replacement: molecular pathology and clinical management - Donald W. Howie; Susan D. Neale; David R. Haynes; Oksana T. Holubowycz; Margaret A. McGee; Lucian B. Solomon; Stuart A. Callary; Gerald J. Atkins; David M. Findlay (Inflammopharmacology, 2013)

Cycling time to failure is better maintained by cold than contrast or thermoneutral lower-body water immersion in normothermia - David Crampton; Bernard Donne; Stuart A. Warmington; Mikel Egaña (European Journal of Applied Physiology, 2013)

Occupational transitions in three coastal villages in Central Java, Indonesia, in the context of sea level rise: a case study - Vijai Joseph; Alec Thornton; Stuart Pearson; David Paull (Natural Hazards, 2013)

Milling plant and soil material in plastic tubes over-estimates carbon and under-estimates nitrogen concentrations - Stuart W. Smith; A. H. Jean Robertson; Andrew A. Meharg; Robin J. Pakeman; David Johnson; Sarah J. Woodin; René van der Wal (Plant and Soil, 2013)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

Magnetic Resonance Spectroscopy of the Normal Cerebellum: What Degree of Variability Can Be Expected? - Stuart Currie; Marios Hadjivassiliou; Iain David Wilkinson; Paul David Griffiths; Nigel Hoggard (The Cerebellum, 2013)

Evaluating the effectiveness of conservation site networks under climate change: accounting for uncertainty - Robert Bagchi; Mike Crosby; Brian Huntley; David G. Hole; Stuart H. M. Butchart; Yvonne Collingham; Mohit Kalra; Jagadish Rajkumar; Asad Rahmani; Mitra Pandey; Hum Gurung; Le Trong Trai; et al. (Global Change Biology, 2013)
We forecasted potential impacts of climate change on the ability of a network of key sites for bird conservation (Important Bird Areas; IBA s) to provide suitable climate for 370 bird species of current conservation concern in two Asian biodiversity hotspots: the Eastern Himalaya and Lower Mekong. Comparable studies have largely not accounted for uncertainty, which may lead to inappropriate conclusions. We quantified the contribution of four sources of variation (choice of general circulation models, emission scenarios and species distribution modelling methods and variation in species distribution data) to uncertainty in forecasts and tested if our projections were robust to these uncertainties. Declines in the availability of suitable climate within the IBA network by 2100 were forecast as ‘extremely likely’ for 45% of species, whereas increases were projected for only 2%. Thus, we predict almost 24 times as many ‘losers’ as ‘winners’. However, for no species was suitable climate ‘extremely likely’ to be completely lost from the network. Considerable turnover (median = 43%, 95% CI = 35–69%) in species compositions of most IBA s were projected by 2100. Climatic conditions in 47% of IBA s were projected as ‘extremely likely’ to become suitable for fewer priority species. However, no IBA was forecast to become suitable for more species. Variation among General Circulation Models and Species Distribution Models contributed most to uncertainty among forecasts. This uncertainty precluded firm conclusions for 53% of species and IBA s because 95% confidence intervals included projections of no change. Considering this uncertainty, however, allows robust recommendations concerning the remaining species and IBA s. Overall, while the IBA network will continue to sustain bird conservation, climate change will modify which species each site will be suitable for. Thus, adaptive management of the network, including modified site conservation strategies and facilitating species' movement among sites, is critical to ensure effective future conservation.

Long Term Performance of Hydrogeochemical Riverine Mine Tailings Deposition at Freeport Indonesia - Yuni Rusdinar; Mansour Edraki; Thomas Baumgartl; David Mulligan; Stuart Miller (Mine Water and the Environment, 2013)

Observations and implications of damage from the magnitude Mw 6.3 Christchurch, New Zealand earthquake of 22 February 2011 - Sean Wilkinson; Damian Grant; Elizabeth Williams; Sara Paganoni; Stuart Fraser; David Boon; Anna Mason; Matthew Free (Bulletin of Earthquake Engineering, 2013)

Population dynamics of invading freshwater fish: common carp (Cyprinus carpio) in the Murray-Darling Basin, Australia - David M. Forsyth; John D. Koehn; Darryl I. MacKenzie; Ivor G. Stuart (Biological Invasions, 2013)

NM23 deficiency promotes metastasis in a UV radiation-induced mouse model of human melanoma - Stuart G. Jarrett; Marian Novak; Nathan Harris; Glenn Merlino; Andrezj Slominski; David M. Kaetzel (Clinical & Experimental Metastasis, 2013)

Littoral‐zone influences on particulate organic matter composition along the freshwater‐tidal Hudson River, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2012)
A multi‐tracer approach was applied to particulate organic material (POM) biogeochemistry along a 165‐km transect of the freshwater‐tidal portion of the Hudson River estuary (HRE). Elemental carbon and nitrogen, stable isotopes, chlorophyll a , and lignin phenols were measured monthly at a mid‐estuary station from August to November 2007, and monthly at the same station and 3–5 additional stations in 2008. POM at stations proximal to major tidal wetland and aquatic vegetation (WETAV) zones showed ∼ 2‰ higher carbon isotopic signature of particulate organic carbon ( δ 13 C POC ), ∼ 3‰ higher nitrogen isotopic signature of particulate nitrogen ( δ 15 N PN ), elevated chlorophyll a levels, and up to 3‐fold increases in Λ 8 ‐lignin phenols indicative of relatively fresh plant matter. This prominent shift in POM composition suggests that WETAV areas supply compositionally unique organic matter along the HRE, especially during low flow. Based on shifts in geochemical tracers downstream of the largest WETAV zone, this POM appears to be readily incorporated, metabolized, and/or deposited to bed sediments. Despite representing

Erratum to: Microalgal fatty acid composition: implications for biodiesel quality - Graham Robert Stansell; Vincent Myles Gray; Stuart David Sym (Journal of Applied Phycology, 2012)

Microalgal fatty acid composition: implications for biodiesel quality - Graham Robert Stansell; Vincent Myles Gray; Stuart David Sym (Journal of Applied Phycology, 2012)

Rodenticide exposure in wood mouse and house mouse populations on farms and potential secondary risk to predators - David G. Tosh; Robbie A. McDonald; Stuart Bearhop; Neville R. Llewellyn; W. Ian Montgomery; Richard F. Shore (Ecotoxicology, 2012)

Biodiversity in Hudson River shore zones: influence of shoreline type and physical structure - David L. Strayer; Stuart E. G. Findlay; Daniel Miller; Heather M. Malcom; David T. Fischer; Thomas Coote (Aquatic Sciences, 2012)

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Rise of the generalists: evidence for climate driven homogenization in avian communities - Catherine M. Davey; Dan E. Chamberlain; Stuart E. Newson; David G. Noble; Alison Johnston (Global Ecology and Biogeography, 2012)
Aims Biogeographical evidence suggests a strong link between climate and patterns of species diversity, and climate change is known to cause range shifts. However, there is little understanding of how shifts affect community composition and we lack empirical evidence of recent impacts of climate change on the diversity of vertebrates. Using a long‐term comprehensive dataset on bird abundance, we explore recent patterns of change in different components of species diversity and avian communities, and postulate a process to explain the observed changes in diversity and specialization. Location Britain. Methods We used Breeding Bird Survey data for Britain from 1994 to 2006 to calculate site‐specific diversity and community specialization indices. We modelled these indices using generalized additive models to examine the relationship between local climate and spatial and temporal trends in community metrics and the relationship between changes in diversity and specialization. Results Local temperature was positively associated with alpha diversity, which increased over the study period, supporting empirical and theoretical predictions of the effect of climate warming. Diversity increased in all habitats, but the rate of increase was greatest in upland areas. However, temperature was negatively associated with community specialization indices, which declined over the same period. Our modelling revealed a nonlinear relationship between community specialization and species diversity. Main conclusions Our models of diversity and specialization provide stark empirical evidence for a link between warming climate and community homogenization. Over a 13‐year period of warming temperatures, diversity indices increased while average community specialization decreased. We suggest that the observed diversity increases were most likely driven by range expansion of generalist species and that future warming is likely to increase homogenization of community structure. When assessed in combination, diversity and specialization measures provide a powerful index for monitoring the impacts of climate change.

Global threats to pinnipeds - Kit M. Kovacs; Alex Aguilar; David Aurioles; Vladimir Burkanov; Claudio Campagna; Nick Gales; Tom Gelatt; Simon D. Goldsworthy; Simon J. Goodman; Greg J. G. Hofmeyr; Tero Härkönen; Lloyd Lowry; et al. (Marine Mammal Science, 2012)

Temporal turnover in the composition of tropical tree communities: functional determinism and phylogenetic stochasticity - Nathan G. Swenson; James C. Stegen; Stuart J. Davies; David L. Erickson; Jimena Forero-Montaña; Allen H. Hurlbert; W. John Kress; Jill Thompson; María Uriarte; S. Joseph Wright; Jess K. Zimmerman (Ecology, 2012)
The degree to which turnover in biological communities is structured by deterministic or stochastic factors and the identities of influential deterministic factors are fundamental, yet unresolved, questions in ecology. Answers to these questions are particularly important for projecting the fate of forests with diverse disturbance histories worldwide. To uncover the processes governing turnover we use species‐level molecular phylogenies and functional trait data sets for two long‐term tropical forest plots with contrasting disturbance histories: one forest is older‐growth, and one was recently disturbed. Having both phylogenetic and functional information further allows us to parse out the deterministic influences of different ecological filters. With the use of null models we find that compositional turnover was random with respect to phylogeny on average, but highly nonrandom with respect to measured functional traits. Furthermore, as predicted by a deterministic assembly process, the older‐growth and disturbed forests were characterized by less than and greater than expected functional turnover, respectively. These results suggest that the abiotic environment, which changes due to succession in the disturbed forest, strongly governs the temporal dynamics of disturbed and undisturbed tropical forests. Predicting future changes in the composition of disturbed and undisturbed forests may therefore be tractable when using a functional‐trait‐based approach.

Downscaling and visioning of mountain snow packs and other climate change implications in North Vancouver, British Columbia - Stewart Jay Cohen; Stephen Sheppard; Alison Shaw; David Flanders; Sarah Burch; Bill Taylor; David Hutchinson; Alex Cannon; Stuart Hamilton; Brent Burton; Jeff Carmichael (Mitigation and Adaptation Strategies for Global Change, 2012)

Multiple mechanisms underlie metastasis suppressor function of NM23-H1 in melanoma - Marian Novak; Stuart G. Jarrett; Joseph R. McCorkle; Isabel Mellon; David M. Kaetzel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Inducible expression of TGFβ, Snail and Zeb1 recapitulates EMT in vitro and in vivo in a NSCLC model - Gretchen M. Argast; Joseph S. Krueger; Stuart Thomson; Isabela Sujka-Kwok; Krista Carey; Stacia Silva; Matthew O’Connor; Peter Mercado; Iain J. Mulford; G. David Young; Regina Sennello; Robert Wild; et al. (Clinical & Experimental Metastasis, 2011)

An Assessment of Three Harpacticoid Copepod Species for Use in Ecotoxicological Testing - Daniel J. Ward; Victor Perez-Landa; David A. Spadaro; Stuart L. Simpson; Dianne F. Jolley (Archives of Environmental Contamination and Toxicology, 2011)

Low Temperature Geothermal Applications as Enablers of Sustainable Development: Practical Case Studies from Australia and UK - Edward Oldmeadow; Dora Marinova; David Birks; Steven Whittall; Stuart Brown (Water Resources Management, 2011)

A framework for studying transient dynamics of population projection matrix models - Iain Stott; Stuart Townley; David James Hodgson (Ecology Letters, 2011)
Ecology Letters (2011) 14 : 959–970 Abstract Empirical models are central to effective conservation and population management, and should be predictive of real‐world dynamics. Available modelling methods are diverse, but analysis usually focuses on long‐term dynamics that are unable to describe the complicated short‐term time series that can arise even from simple models following ecological disturbances or perturbations. Recent interest in such transient dynamics has led to diverse methodologies for their quantification in density‐independent, time‐invariant population projection matrix (PPM) models, but the fragmented nature of this literature has stifled the widespread analysis of transients. We review the literature on transient analyses of linear PPM models and synthesise a coherent framework. We promote the use of standardised indices, and categorise indices according to their focus on either convergence times or transient population density, and on either transient bounds or case‐specific transient dynamics. We use a large database of empirical PPM models to explore relationships between indices of transient dynamics. This analysis promotes the use of population inertia as a simple, versatile and informative predictor of transient population density, but criticises the utility of established indices of convergence times. Our findings should guide further development of analyses of transient population dynamics using PPMs or other empirical modelling techniques.

Alternative (non-animal) methods for cosmetics testing: current status and future prospects—2010 - Sarah Adler; David Basketter; Stuart Creton; Olavi Pelkonen; Jan van Benthem; Valérie Zuang; Klaus Ejner Andersen; Alexandre Angers-Loustau; Aynur Aptula; Anna Bal-Price; Emilio Benfenati; Ulrike Bernauer; et al. (Archives of Toxicology, 2011)

Toward a Management Framework for Networks of Protected Areas in the Face of Climate Change - DAVID G. HOLE; BRIAN HUNTLEY; JULIUS ARINAITWE; STUART H. M. BUTCHART; YVONNE C. COLLINGHAM; LINCOLN D. C. FISHPOOL; DEBORAH J. PAIN; STEPHEN G. WILLIS (Conservation Biology, 2011)
Networks of sites of high importance for conservation of biological diversity are a cornerstone of current conservation strategies but are fixed in space and time. As climate change progresses, substantial shifts in species’ ranges may transform the ecological community that can be supported at a given site. Thus, some species in an existing network may not be protected in the future or may be protected only if they can move to sites that in future provide suitable conditions. We developed an approach to determine appropriate climate‐change adaptation strategies for individual sites within a network that was based on projections of future changes in the relative proportions of emigrants (species for which a site becomes climatically unsuitable), colonists (species for which a site becomes climatically suitable), and persistent species (species able to remain within a site despite the climatic change). Our approach also identifies key regions where additions to a network could enhance its future effectiveness. Using the sub‐Saharan African Important Bird Area (IBA) network as a case study, we found that appropriate conservation strategies for individual sites varied widely across sub‐Saharan Africa, and key regions where new sites could help increase network robustness varied in space and time. Although these results highlight the potential difficulties within any planning framework that seeks to address climate‐change adaptation needs, they demonstrate that such planning frameworks are necessary, if current conservation strategies are to be adapted effectively, and feasible, if applied judiciously.

A new dawn for industrial photosynthesis - Dan E. Robertson; Stuart A. Jacobson; Frederick Morgan; David Berry; George M. Church; Noubar B. Afeyan (Photosynthesis Research, 2011)

Earth stewardship: a strategy for social–ecological transformation to reverse planetary degradation - F. Stuart Chapin; Steward T. A. Pickett; Mary E. Power; Robert B. Jackson; David M. Carter; Clifford Duke (Journal of Environmental Studies and Sciences, 2011)

A systems view of epithelial–mesenchymal transition signaling states - Stuart Thomson; Filippo Petti; Izabela Sujka-Kwok; Peter Mercado; James Bean; Melissa Monaghan; Sean L. Seymour; Gretchen M. Argast; David M. Epstein; John D. Haley (Clinical & Experimental Metastasis, 2011)

Solar energy harvesting in the epicuticle of the oriental hornet (Vespa orientalis) - Marian Plotkin; Idan Hod; Arie Zaban; Stuart A. Boden; Darren M. Bagnall; Dmitry Galushko; David J. Bergman (The Science of Nature, 2010)

Greenhouse gas emissions from Australian open-cut coal mines: contribution from spontaneous combustion and low-temperature oxidation - Stuart J. Day; John N. Carras; Robyn Fry; David J. Williams (Environmental Monitoring and Assessment, 2010)

Wetland‐driven shifts in suspended particulate organic matter composition of the Hudson River estuary, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2010)
Elemental carbon and nitrogen, stable isotopes, and lignin phenols were quantified for suspended particulate material exchanging between Tivoli Bays wetlands and the main stem of the freshwater‐tidal Hudson River estuary (HRE) across a tidal cycle, seasonally in 2006 and monthly in 2007 during the ice‐free portion of the year. Temporal shifts in organic matter (OM) composition ranged from 33.1 to 247.6 mg g −1 particulate organic carbon (POC), ‐34.7‰ to ‐27.2‰ stable carbon isotopic signature of POC (δ 13 C POC ), ‐3.6‰ to 13.6‰ nitrogen isotopic signature of particulate nitrogen (δ 15 N PN ), and 0.8 to 25.0 mg per 100 mg OC lignin phenols. From May to August, the wetlands transferred abundant (up to 247.6 mg g −1 ), chemically distinctive (δ 13 C POC as depleted as ‐34.7‰) particulate OM to the HRE, particularly Tivoli South Bay. We estimated a net export of > 60 Mg km −2 yr −1 POC from Tivoli Bays into the HRE. Mixing model iterations indicated that planktonic OM was the dominant source (50% to 86%) during summertime, while contributions from allochthonous and planktonic OM during other seasons were roughly equivalent (~ 38%). Taken together, both geochemical data and mixing modeling underscore the function and value of HRE tidal wetlands as major generators of compositionally unique and labile POC for the estuarine carbon budget. In a broader context, lateral aquatic connections with tidal wetlands at seasonal or localized scales may overshadow internal or upland influences on OM composition, production, and processing in estuaries; a latent but key consideration when deciphering temporal and longitudinal trends.

A model of direction selectivity in the starburst amacrine cell network - Germán A. Enciso; Michael Rempe; Andrey V. Dmitriev; Konstantin E. Gavrikov; David Terman; Stuart C. Mangel (Journal of Computational Neuroscience, 2010)

Ecology of freshwater shore zones - David L. Strayer; Stuart E. G. Findlay (Aquatic Sciences, 2010)

Potential impact of grey squirrels Sciurus carolinensis on woodland bird populations in England - Stuart E. Newson; David I. Leech; Chris M. Hewson; Humphrey Q. P. Crick; Phil V. Grice (Journal of Ornithology, 2010)

Stability in temperate reef communities over a decadal time scale despite concurrent ocean warming - RICK D. STUART‐SMITH; NEVILLE S. BARRETT; DAVID G. STEVENSON; GRAHAM J. EDGAR (Global Change Biology, 2010)
Despite increasing scientific and public concerns on the potential impacts of global ocean warming on marine biodiversity, very few empirical data on community‐level responses to rising water temperatures are available other than for coral reefs. This study describes changes in temperate subtidal reef communities over decadal and regional scales in a location that has undergone considerable warming in recent decades and is forecast to be a ‘hotspot’ for future warming. Plant and animal communities at 136 rocky reef sites around Tasmania (south‐east Australia) were censused between 1992 and 1995, and again in 2006 and 2007. Despite evidence of major ecological changes before the period of study, reef communities appeared to remain relatively stable over the past decade. Multivariate analyses and univariate metrics of biotic communities revealed few changes with time, although some species‐level responses could be interpreted as symptomatic of ocean warming. These included fishes detected in Tasmania only in recent surveys and several species with warmer water affinities that appeared to extend their distributions further south. The most statistically significant changes observed in species abundances, however, were not related to their biogeographical affinities. The majority of species with changing abundance possessed lower to mid‐range abundances rather than being common, raising questions for biodiversity monitoring and management. We suggest that our study encompassed a relatively stable period following more abrupt change, and that community responses to ocean warming may follow nonlinear, step‐like trajectories.

Soil drying and nitrogen availability modulate carbon and water exchange over a range of annual precipitation totals and grassland vegetation types - SAMUEL B. St. CLAIR; ERIKA A. SUDDERTH; MARC L. FISCHER; MARGARET S. TORN; STEPHANIE A. STUART; ROHIT SALVE; DENNIS L. EGGETT; DAVID D. ACKERLY (Global Change Biology, 2009)
Increased intensity in precipitation events and longer periods of water deficit are predicted as a general trend under future climate scenarios with potentially large effects on terrestrial ecosystem function. The primary objective of this study was to understand how variation in the intensity of precipitation inputs followed by intermittent soil drying events influence leaf and ecosystem carbon dioxide (CO 2 ) and water exchange in a California annual grassland mesocosm experiment. We further examined how nitrogen (N) availability, and differences in plant community composition (grass‐forb combinations) affected gas exchange responses to the precipitation treatments. Net ecosystem CO 2 exchange (NEE) and evapotranspiration (ET) increased significantly with greater precipitation and were positively correlated with soil moisture. A repeated 10‐day soil drying period, following 11 days of watering, strongly depressed NEE over a range of annual precipitation totals (297, 657 and 987 mm), and plant community types. Ecosystem dark respiration ( R e ) and leaf level photosynthesis ( A max ) showed greater sensitivity to periods of soil drying in the low precipitation plots (297 mm). N additions significantly increased NEE and R e , particularly as water availability was increased. Across the range of precipitation totals and plant community types, intermittent periods of soil moisture deficit and native soil N availability constrained leaf and ecosystem level CO 2 exchange, while the influence on water vapor exchange was less pronounced.

Patterns and rules for sensitivity and elasticity in population projection matrices - David Carslake; Stuart Townley; David J. Hodgson (Ecology, 2009)
Sensitivity and elasticity analysis of population projection matrices (PPMs) are established tools in the analysis of structured populations, allowing comparison of the contributions made by different demographic rates to population growth. In some commonly used structures of PPM, however, there are mathematically inevitable patterns in the relative sensitivity and elasticity of certain demographic rates. We take a simulation approach to investigate these mathematical constraints for a range of PPM models. Our results challenge some previously proposed constraints on sensitivity and elasticity. We also identify constraints beyond those that have already been proven mathematically and promote them as candidates for future mathematical proof. A general theme among these rules is that changes to the demographic rates of older or larger individuals have less impact on population growth than do equivalent changes among younger or smaller individuals. However, the validity of these rules in each case depends on the choice between sensitivity and elasticity, the growth rate of the population, and the PPM structure used. If the structured population conforms perfectly to the assumptions of the PPM used to model it, the rules we describe represent biological reality, allowing us to prioritize management strategies in the absence of detailed demographic data. Conversely, if the model is a poor fit to the population (specifically, if demographic rates within stages are heterogeneous), such analyses could lead to inappropriate management prescriptions. Our results emphasize the importance of choosing a structured population model that fits the demographics of the population.

Potential contributions of antimutator activity to the metastasis suppressor function of NM23-H1 - David M. Kaetzel; Joseph R. McCorkle; Marian Novak; Mengmeng Yang; Stuart G. Jarrett (Molecular and Cellular Biochemistry, 2009)

Microstructures of Antarctic cidaroid spines: diversity of shapes and ectosymbiont attachments - Bruno David; Stuart R. Stock; Francesco De Carlo; Vincent Hétérier; Chantal De Ridder (Marine Biology, 2009)

Projected impacts of climate change on a continent‐wide protected area network - David G. Hole; Stephen G. Willis; Deborah J. Pain; Lincoln D. Fishpool; Stuart H. M. Butchart; Yvonne C. Collingham; Carsten Rahbek; Brian Huntley (Ecology Letters, 2009)
Despite widespread concern, the continuing effectiveness of networks of protected areas under projected 21st century climate change is uncertain. Shifts in species’ distributions could mean these resources will cease to afford protection to those species for which they were originally established. Using modelled projected shifts in the distributions of sub‐Saharan Africa’s entire breeding avifauna, we show that species turnover across the continent’s Important Bird Area (IBA) network is likely to vary regionally and will be substantial at many sites (> 50% at 42% of IBAs by 2085 for priority species). Persistence of suitable climate space across the network as a whole, however, is notably high, with 88–92% of priority species retaining suitable climate space in ≥ 1 IBA(s) in which they are currently found. Only 7–8 priority species lose climatic representation from the network. Hence, despite the likelihood of significant community disruption, we demonstrate that rigorously defined networks of protected areas can play a key role in mitigating the worst impacts of climate change on biodiversity.

Management of Concentrated Waste Streams from High-Pressure Membrane Water Treatment Systems - Stuart J. Khan; David Murchland; Michelle Rhodes; T. David Waite (Critical Reviews in Environmental Science and Technology, 2009)

Pragmatism and Practice in Classifying Threats: Reply to Balmford et al. - NICK SALAFSKY; STUART H.M. BUTCHART; DANIEL SALZER; ALISON J. STATTERSFIELD; RACHEL NEUGARTEN; CRAIG HILTON‐TAYLOR; BEN COLLEN; LAWRENCE L. MASTER; SHEILA O’CONNOR; DAVID WILKIE (Conservation Biology, 2009)

Kinase switching in mesenchymal-like non-small cell lung cancer lines contributes to EGFR inhibitor resistance through pathway redundancy - Stuart Thomson; Filippo Petti; Izabela Sujka-Kwok; David Epstein; John D. Haley (Clinical & Experimental Metastasis, 2008)

COMPARATIVE ECOLOGY OF NORTH ATLANTIC SHORES: DO DIFFERENCES IN PLAYERS MATTER FOR PROCESS? - Stuart R. Jenkins; Pippa Moore; Michael T. Burrows; David J. Garbary; Stephen J. Hawkins; Agnar Ingólfsson; Kenneth P. Sebens; Paul V. R. Snelgrove; David S. Wethey; Sarah A. Woodin (Ecology, 2008)
The contrasting histories of the western and eastern shores of the North Atlantic Ocean provide an excellent opportunity to consider the implications of past events for present ecological processes and the functioning of marine ecosystems. Similarities and differences in assemblage composition have been driven by large‐scale events, such as the trans‐Arctic interchange, which has shaped the species pool, and cycles of glaciation, which have determined phases of local or regional extinction and colonization. More recently, anthropogenically induced invasions and local extinctions have significantly altered biogeographic distributions. Here we consider for both hard and soft substrata how the presence or absence of key taxa influences the outcomes of trophic and other biological interactions, and evaluate the consequences for community structure and ecosystem functioning. On intertidal hard substratum shores, biodiversity of epilithic microphagous grazers differs across latitudinal and longitudinal scales. Diversity is high in southern Europe but declines to the north and across the Atlantic. Lower diversity and the absence of patellid limpets in Iceland and the northwest Atlantic compared to Europe result in differences in consumer pressure, and an apparent contrast in the importance of herbivory vs. competitive interactions and predation pressure as community structuring processes. Interestingly, despite differences in “process,” community patterns are remarkably similar between the east and west. On soft sediment shores, there are conspicuous geographic differences in importance of bioturbators and large digging predators. Hemichordates can be abundant and important infaunal bioturbators in the western Atlantic, but they generally play a much reduced role in the eastern Atlantic. In addition, the number and diversity of digging predators on western Atlantic shores is high; the horseshoe crab, swimming portunid crabs, large whelks, excavating waterfowl, and an abundance of skates and rays exert intense predation pressure and associated biogenic disturbance to sediments. In Europe, except for excavating waterfowl these taxa are rare or absent. Thus, the importance of large, biological agents of disturbance is lower on European shores as a consequence of both recent anthropogenic pressure and natural processes over larger time scales. Consideration of key structuring taxa over the Atlantic shows that human‐mediated transport has had considerable influence. Faunas on both sides of the Atlantic are becoming more similar to the point that some of the key differences in assemblage composition and hence community organization have blurred. Recent introductions as well as planned experimental manipulations provide the opportunity to understand the role of species identity in determining community structure and ecosystem functioning over large spatial scales; the North Atlantic may be an ideal test system to explore these areas.

Bypassing cellular EGF receptor dependence through epithelial-to-mesenchymal-like transitions - Sharon Barr; Stuart Thomson; Elizabeth Buck; Suzanne Russo; Filippo Petti; Izabela Sujka-Kwok; Alexandra Eyzaguirre; Maryland Rosenfeld-Franklin; Neil W. Gibson; Mark Miglarese; David Epstein; Kenneth K. Iwata; et al. (Clinical & Experimental Metastasis, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Predicting Carbon and Nutrient Transformations in Tidal Freshwater Wetlands of the Hudson River - Alicia Arrigoni; Stuart Findlay; David Fischer; Klement Tockner (Ecosystems, 2008)

A Standard Lexicon for Biodiversity Conservation: Unified Classifications of Threats and Actions - NICK SALAFSKY; DANIEL SALZER; ALISON J. STATTERSFIELD; CRAIG HILTON‐TAYLOR; RACHEL NEUGARTEN; STUART H. M. BUTCHART; BEN COLLEN; NEIL COX; LAWRENCE L. MASTER; SHEILA O'CONNOR; DAVID WILKIE (Conservation Biology, 2008)
An essential foundation of any science is a standard lexicon. Any given conservation project can be described in terms of the biodiversity targets, direct threats, contributing factors at the project site, and the conservation actions that the project team is employing to change the situation. These common elements can be linked in a causal chain, which represents a theory of change about how the conservation actions are intended to bring about desired project outcomes. If project teams want to describe and share their work and learn from one another, they need a standard and precise lexicon to specifically describe each node along this chain. To date, there have been several independent efforts to develop standard classifications for the direct threats that affect biodiversity and the conservation actions required to counteract these threats. Recognizing that it is far more effective to have only one accepted global scheme, we merged these separate efforts into unified classifications of threats and actions, which we present here. Each classification is a hierarchical listing of terms and associated definitions. The classifications are comprehensive and exclusive at the upper levels of the hierarchy, expandable at the lower levels, and simple, consistent, and scalable at all levels. We tested these classifications by applying them post hoc to 1191 threatened bird species and 737 conservation projects. Almost all threats and actions could be assigned to the new classification systems, save for some cases lacking detailed information. Furthermore, the new classification systems provided an improved way of analyzing and comparing information across projects when compared with earlier systems. We believe that widespread adoption of these classifications will help practitioners more systematically identify threats and appropriate actions, managers to more efficiently set priorities and allocate resources, and most important, facilitate cross‐project learning and the development of a systematic science of conservation.

Landowner Willingness to Engage in Long-Term Timber Leases in West Virginia, USA - David W. McGill; Shawn T. Grushecky; Stuart Moss; Chad Pierskalla; Al Schuler (Small-scale Forestry, 2008)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2008)

Trends in landslide occurrence in Nepal - David N. Petley; Gareth J. Hearn; Andrew Hart; Nicholas J. Rosser; Stuart A. Dunning; Katie Oven; Wishart A. Mitchell (Natural Hazards, 2007)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2007)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Contaminants in tilapia (Oreochromis mossambicus) from the Salton Sea, California, in relation to human health, piscivorous birds and fish meal production - Marie F. Moreau; Janie Surico-Bennett; Marie Vicario-Fisher; David Crane; Russel Gerads; Richard M. Gersberg; Stuart H. Hurlbert (Hydrobiologia, 2007)

Interaction of hydrology and nutrient limitation in the Ridge and Slough landscape of the southern Everglades - Michael S. Ross; Sherry Mitchell-Bruker; Jay P. Sah; Stuart Stothoff; Pablo L. Ruiz; David L. Reed; Kris Jayachandran; Charles L. Coultas (Hydrobiologia, 2006)

Characterizing a tropical deforestation wave: a dynamic spatial analysis of a deforestation hotspot in the Colombian Amazon - ANDRES ETTER; CLIVE MCALPINE; STUART PHINN; DAVID PULLAR; HUGH POSSINGHAM (Global Change Biology, 2006)
Tropical deforestation is the major contemporary threat to global biodiversity, because a diminishing extent of tropical forests supports the majority of the Earth's biodiversity. Forest clearing is often spatially concentrated in regions where human land use pressures, either planned or unplanned, increase the likelihood of deforestation. However, it is not a random process, but often moves in waves originating from settled areas. We investigate the spatial dynamics of land cover change in a tropical deforestation hotspot in the Colombian Amazon. We apply a forest cover zoning approach which permitted: calculation of colonization speed; comparative spatial analysis of patterns of deforestation and regeneration; analysis of spatial patterns of mature and recently regenerated forests; and the identification of local‐level hotspots experiencing the fastest deforestation or regeneration. The colonization frontline moved at an average of 0.84 km yr −1 from 1989 to 2002, resulting in the clearing of 3400 ha yr −1 of forests beyond the 90% forest cover line. The dynamics of forest clearing varied across the colonization front according to the amount of forest in the landscape, but was spatially concentrated in well‐defined ‘local hotspots’ of deforestation and forest regeneration. Behind the deforestation front, the transformed landscape mosaic is composed of cropping and grazing lands interspersed with mature forest fragments and patches of recently regenerated forests. We discuss the implications of the patterns of forest loss and fragmentation for biodiversity conservation within a framework of dynamic conservation planning.

Indirect effects of algae on coral: algae‐mediated, microbe‐induced coral mortality - Jennifer E. Smith; Morrigan Shaw; Rob A. Edwards; David Obura; Olga Pantos; Enric Sala; Stuart A. Sandin; Steven Smriga; Mark Hatay; Forest L. Rohwer (Ecology Letters, 2006)
Declines in coral cover are generally associated with increases in the abundance of fleshy algae. In many cases, it remains unclear whether algae are responsible, directly or indirectly, for coral death or whether they simply settle on dead coral surfaces. Here, we show that algae can indirectly cause coral mortality by enhancing microbial activity via the release of dissolved compounds. When coral and algae were placed in chambers together but separated by a 0.02 μ m filter, corals suffered 100% mortality. With the addition of the broad‐spectrum antibiotic ampicillin, mortality was completely prevented. Physiological measurements showed complementary patterns of increasing coral stress with proximity to algae. Our results suggest that as human impacts increase and algae become more abundant on reefs a positive feedback loop may be created whereby compounds released by algae enhance microbial activity on live coral surfaces causing mortality of corals and further algal growth.

The GeoProfile metadata, exposure of instruments, and measurement bias in climatic record revisited - Rezaul Mahmood; Stuart A. Foster; David Logan (International Journal of Climatology, 2006)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)

Accumulation of Knowledge and Changes in Red List Classifications within the Family Galliformes1980–2004 - David C. Lee; Stuart J. Marsden (Biodiversity and Conservation, 2006)

Endogenous production of endo-β-1,4-glucanase by decapod crustaceans - Stuart M. Linton; Peter Greenaway; David W. Towle (Journal of Comparative Physiology B, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Multi-Scale Controls on Water Quality Effects of Submerged Aquatic Vegetation in the Tidal Freshwater Hudson River - Stuart E. G. Findlay; William C. Nieder; Elizabeth A. Blair; David T. Fischer (Ecosystems, 2006)

Temporal Changes between Ecological Regimes in a Range of Primary and Secondary Salinised Wetlands - Karin Strehlow; Jenny Davis; Lien Sim; Jane Chambers; Stuart Halse; David Hamilton; Pierre Horwitz; Arthur McComb; Ray Froend (Hydrobiologia, 2005)

The EPAS1 gene influences the aerobic–anaerobic contribution in elite endurance athletes - Jennifer Henderson; Jason M. Withford-Cave; David L. Duffy; Stuart J. Cole; Nicole A. Sawyer; Jason P. Gulbin; Allan Hahn; Ronald J. Trent; Bing Yu (Human Genetics, 2005)

Genetic Typing of Classical Swine Fever Viruses from Lao PDR by Analysis of the 5′ Non-Coding Region - Stuart D. Blacksell; Syseng Khounsy; David B. Boyle; Laurence J. Gleeson; Harvey A. Westbury; John S. Mackenzie (Virus Genes, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

The Event Book System: A Community-based Natural Resource Monitoring System from Namibia - Greg Stuart-Hill; Richard Diggle; Bevan Munali; Jo Tagg; David Ward (Biodiversity and Conservation, 2005)

Refinement and application of a conductiometric standpipe technique for measuring interstitial flow velocity in salmonid spawning gravels - Stuart M. Greig; Paul A. Carling; David A. Sear; Les J. Whitcombe (Hydrobiologia, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Three-dimensional Structure of an Old-growth Pseudotsuga-Tsuga Canopy and Its Implications for Radiation Balance, Microclimate, and Gas Exchange - Geoffrey G. Parker; Mark E. Harmon; Michael A. Lefsky; Jiquan Chen; Robert Van Pelt; Stuart B. Weis; Sean C. Thomas; William E. Winner; David C. Shaw; Jerry F. Frankling (Ecosystems, 2004)

Delineation of complex chromosomal rearrangements: evidence for increased complexity - Caroline Astbury; Laurie A. Christ; David J. Aughton; Suzanne B. Cassidy; Atsuko Fujimoto; Beth A. Pletcher; Irwin A. Schafer; Stuart Schwartz (Human Genetics, 2004)

Analysis and comparison of the microbial community structures of two enrichment cultures capable of reductively dechlorinating TCE and cis ‐DCE - April Z. Gu; Brian P. Hedlund; James T. Staley; Stuart E. Strand; H. David Stensel (Environmental Microbiology, 2004)
Summary In order to study the effect of different chloroethenes (electron acceptors) on the bacterial composition of dechlorinating communities, two reductive dechlorinating enrichment cultures were developed that were able to reduce trichloroethene (TCE) and cis ‐1,2‐dichloroethene ( cis ‐DCE) to ethene using hydrogen as electron donor, respectively. The inoculum for the cultures was material from a methanogenic fluidized bed reactor (FBR), which was originally seeded with digester sludge and showed a stable capacity for tetrachloroethene (PCE) reduction to ethene for over six years. Molecular methods were used to determine and compare the microbial communities of these two enrichment cultures. A clone library of bacterial 16S rRNA genes was generated for each enrichment. The clones were screened into different groups by restriction fragment length polymorphism (RFLP) analysis using two different four base pair recognition restriction enzymes. A total of 12 sequence types were identified by phylogenetic analysis of nearly complete 16S rDNA sequences (∼1450 bp). The sequences were affiliated with six recognized phyla of the domain Bacteria: Firmicutes (low G+C Gram‐positives), Chloroflexi (green non‐sulphur bacteria), Actinobacteria (high G+C Gram‐positives), Bacteroidetes (Cytophaga‐Flexibacter‐Bacteroides), Nitrospira and Spirochaetes. The results led to the identification of an organism closely related to Dehalococcoides ethenogenes to be the presumptive dechlorinator in both enrichments. Different electron acceptors affected the bacterial diversity and the community profiles of the two enrichments. Most of the sequences identified in our dechlorinating enrichments shared high similarities with sequences previously obtained from other enriched dechlorinating cultures and chlorinated‐compound‐contaminated sediments or aquifers, suggesting these bacteria may have direct or indirect roles in reductive dechlorination.

Translocation Causes Extinction of a Local Population of the Freshwater Shrimp Paratya australiensis - Jane Hughes; Katrina Goudkamp; David Hurwood; Martyn Hancock; Stuart Bunn (Conservation Biology, 2003)
In 1993, as part of another study, we translocated freshwater shrimp ( Paratya australiensis ) between pools from two different subcatchments within the same drainage system in southeast Queensland, Australia. Subsequent analysis of the mitochondrial COI locus revealed that populations in the two subcatchments represented monophyletic lineages that were 6% divergent. Thus, we decided to determine the effects of the translocation on resident populations. After only 7 years, representing seven generations, the resident genotype was extinct at one of the sites. Evidence from analysis of nuclear genes ( allozymes ) and mitochondrial genes ( COI ) suggests that this extreme result may be explained by a mating preference of all females ( resident and translocated ) for translocated males and a low viability of crosses between resident females and translocated males. There is no obvious morphological or behavioral reason for a mating preference. The results of our study provide evidence that deliberate translocations and interbasin water transfers should be treated with caution.

Using LCA to examine greenhouse gas abatement policy - Stuart Ross; David Evans; Michael Webber (The International Journal of Life Cycle Assessment, 2003)

Similar estimates of population genetic composition and sex ratio derived from carcasses and faeces of Eurasian otter Lutra lutra - John F. Dallas; Karen E. Coxon; Tim Sykes; Paul R. F. Chanin; Freda Marshall; David N. Carss; Philip J. Bacon; Stuart B. Piertney; Paul A. Racey (Molecular Ecology, 2003)
Collecting faeces is viewed as a potentially efficient way to sample elusive animals. Nonetheless, any biases in estimates of population composition associated with such sampling remain uncharacterized. The goal of this study was to compare estimates of genetic composition and sex ratio derived from Eurasian otter Lutra lutra spraints (faeces) with estimates derived from carcasses. Twenty per cent of 426 wild‐collected spraints from SW England yielded composite genotypes for 7–9 microsatellites and the SRY gene. The expected number of incorrect spraint genotypes was negligible, given the proportions of allele dropout and false allele detection estimated using paired blood and spraint samples of three captive otters. Fifty‐two different spraint genotypes were detected and compared with genotypes of 70 otter carcasses from the same area. Carcass and spraint genotypes did not differ significantly in mean number of alleles, mean unbiased heterozygosity or sex ratio, although statistical power to detect all but large differences in sex ratio was low. The genetic compositions of carcass and spraint genotypes were very similar according to confidence intervals of θ and two methods for assigning composite genotypes to groups. A distinct group of approximately 11 carcass and spraint genotypes was detected using the latter methods. The results suggest that spraints can yield unbiased estimates of population genetic composition and sex ratio.

The use of life cycle assessment in environmental management - Stuart Ross; David Evans (The International Journal of Life Cycle Assessment, 2002)

Excluding site-specific data from the lca inventory: how this affects life cycle impact assessment - Stuart Ross; David Evans (The International Journal of Life Cycle Assessment, 2002)

How LCA studies deal with uncertainty - Stuart Ross; David Evans; Michael Webber (The International Journal of Life Cycle Assessment, 2002)

Use of Life Cycle Assessment in Environmental Management - Stuart Ross; David Evans (Environmental Management, 2002)

Atmospheric motion systems that influence the redistribution and accumulation of insects on the beaches of the Great Lakes in North America - Scott A. Isard; David A. R. Kristovich; Stuart H. Gage; Carl J. Jones; Neil F. Laird (Aerobiologia, 2001)

Dog MHC alleles containing the human RA shared epitope confer susceptibility to canine rheumatoid arthritis - William Ollier; Lorna Kennedy; Wendy Thomson; Annette Barnes; Susan Bell; David Bennett; John Angles; John Innes; Stuart Carter (Immunogenetics, 2001)

Microhardness and Dislocation Identification Studies on Paracetamol Single Crystals - Stuart Finnie; Korlakunte V. R. Prasad; David B. Sheen; John N. Sherwood (Pharmaceutical Research, 2001)

Sex identification of the Eurasian otter Lutra lutra by PCR typing of spraints - John F. Dallas; David N. Carss; Freda Marshall; Klaus-Peter Koepfli; Hans Kruuk; Philip J. Bacon; Stuart B. Piertney (Conservation Genetics, 2000)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

Isolation and characterization of microsatellite loci in the freshwater gastropod, Biomphalaria glabrata , an intermediate host for Schistosoma mansoni - Catherine S. Jones; Anne E. Lockyer; David Rollinson; Stuart B. Piertney; Leslie R. Noble (Molecular Ecology, 1999)

Predominance of ecophysiological controls on soil CO2 flux in a Minnesota grassland - Joseph M. Craine; David A. Wedin; F. Stuart Chapin (Plant and Soil, 1999)

Diel variation in horizontal distribution of Daphnia and Ceriodaphnia in oligotrophic and mesotrophic lakes with contrasting fish densities - Torben L. Lauridsen; Erik Jeppesen; Stuart F. Mitchell; David M. Lodge; Romi L. Burks (Hydrobiologia, 1999)

Susceptibility of Antarctic krill ( Euphausia superba Dana) to ultraviolet radiation - Stuart J. Newman; Stephen Nicol; David Ritz; Harvey Marchant (Polar Biology, 1999)

Nine new dog DLA-DRB1 alleles identified by sequence-based typing - L. J. Kennedy; Stuart D. Carter; Annette Barnes; Susan Bell; David Bennett; William E. R. Ollier; Wendy Thomson (Immunogenetics, 1998)

O2 uptake during solid-state fermentation in a rotating drum bioreactor - Anna J. Marsh; David A. Mitchell; Deidre M. Stuart; Tony Howes (Biotechnology Letters, 1998)

Original Articles: Sources of Dissolved Organic Carbon Supporting Planktonic Bacterial Production in the Tidal Freshwater Hudson River - Stuart Findlay; Robert L. Sinsabaugh, David T. Fischer (Ecosystems, 1998)

Characterizing sequence variation in the VP1 capsid proteins of foot and mouth disease virus (serotype 0) with respect to virion structure - Daniel Haydon; Susan Lea; Liz Fry; Nick Knowles; Alan R. Samuel; David Stuart; Mark E. J. Woolhouse (Journal of Molecular Evolution, 1998)

Bioaccumulation Factors (BAFs) and Biota to Sediment Accumulation Factors (BSAFs) for PCBs in pike and eels - Stuart J. Harrad; David J. T. Smith (Environmental Science and Pollution Research, 1997)

Measurement of PAN in the Polluted Boundary Layer and Free Troposphere Using a Luminol-NO2 Detector Combined with a Thermal Converter - Chloe Nikitas; Kevin C. Clemitshaw; David E. Oram; Stuart a. Penkett (Journal of Atmospheric Chemistry, 1997)

Identification of new Mamu-DRB alleles using DGGE and direct sequencing - L. A. Knapp; Luis F. Cadavid; Mary E. Eberle; Stuart J. Knechtle; Ronald E. Bontrop; David I. Watkins (Immunogenetics, 1997)

Enzymatic analysis of riverine bacterioplankton production - Robert L. Sinsabaugh; Stuart Findlay; Paula Franchini; David Fischer (Limnology and Oceanography, 1997)
Bacterial production is the entry point for detrital macronutrients into aquatic food webs. Many factors affect productivity, but the heterogeneity of detrital substrates and the diversity of microbial communities confound simple relationships between carbon supply and growth. We tried to link the two by analyzing extracellular enzyme activities. Water samples were collected from three rivers and assayed for bacterial productivity and the activities of eight enzymes. Production varied among systems, peaking at 644, 170, and 68 µ mol C liter ‒1 d ‒1 in the Ottawa (Ohio), Maumee (Ohio), and Hudson (New York) Rivers. V max values were generally correlated with productivity. The mean ratios of productivity per unit peptidase and esterase activity were similar among rivers, whereas carbohydrase and phosphatase ratios varied widely. The data were used to evaluate a model that relates productivity to carbon flow by using enzyme activities as indicators and assuming an optimum resource allocation relationship among C‐, N‐, and P‐acquiring enzymes. The data supported the model, but predictive power was low. Bacterial productivity generally increased with inorganic nutrient availability, but high levels of productivity at any specific eutrophic state required sources of both saccharides and amino acids.

The expression of redox proteins of denitrification inThiosphaera pantotropha grown with oxygen, nitrate, and nitrous oxide as electron acceptors - James W. B. Moir; David J. Richardson; Stuart J. Ferguson (Archives of Microbiology, 1995)

The influence of carbon substrate on the activity of the periplasmic nitrate reductase in aerobically grown Thiosphaera pantotropha - David J. Richardson; Stuart J. Ferguson (Archives of Microbiology, 1992)

Rhodobacter capsulatus strain BK5 possesses a membrane bound respiratory nitrate reductase rather than the periplasmic enzyme found in other strains - Anna L. Ballard; Alastair G. McEwan; David J. Richardson; J. Baz Jackson; Stuart J. Ferguson (Archives of Microbiology, 1990)

Inhibition and killing of fungi by the polyamine oxidase-polyamine system - Stuart M. Levitz; David J. DiBenedetto; Richard D. Diamond (Antonie van Leeuwenhoek, 1990)

The role of auxiliary oxidants in maintaining redox balance during phototrophic growth of Rhodobacter capsulatuspropionate or butyrate - David J. Richardson; Glenn F. King; David J. Kelly; Alastair G. McEwan; Stuart J. Ferguson; J. Barry Jackson (Archives of Microbiology, 1988)

The role of auxiliary oxidants in maintaining redox balance during phototrophic growth of Rhodobacter capsulatus on propionate or butyrate - David J. Richardson; Glenn F. King; David J. Kelly; Alastair G. McEwan; Stuart J. Ferguson; J. Barry Jackson (Archives of Microbiology, 1988)

Renal perfusion dynamics during preservation - Stephen W. Flax; John G. Webster; Stuart J. Updike; David T. Uehling (Annals of Biomedical Engineering, 1978)

The salt relations of Dunaliella - Lesley Joyce Borowitzka; David Stuart Kessly; Austin Duncan Brown (Archives of Microbiology, 1977)